Optical laminate
By using a two-layer adhesive laminate structure with different transmittance in Mini/Micro LED display devices, the problems of reduced luminous efficiency and increased power consumption caused by black encapsulation materials are solved, achieving high luminous efficiency and improved contrast, while preventing metal wiring reflection and RGB color mixing.
Patent Information
- Application Number
- CN202180026271.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-31
- Filing Date
- 2021-03-26
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-03-26
AI Technical Summary
In existing Mini/Micro LED display devices, the reduced visible light transmittance caused by black encapsulation materials leads to decreased luminous efficiency and darkened images. At the same time, increasing luminous efficiency increases power consumption, and it is difficult to balance the anti-reflective function of metal wiring with the prevention of RGB color mixing and the balance of contrast.
A two-layer adhesive stack structure with different transmittance is adopted. The transmittance of the first adhesive layer is lower than that of the second adhesive layer. The first adhesive layer encapsulates the metal wiring and LED chip, while the second adhesive layer is located on the image display side to improve transmittance. Combined with the substrate stack, an optical stack is formed to improve luminous efficiency and contrast.
It improves the luminous efficiency and contrast of Mini/Micro LED display devices, reduces power consumption, and effectively prevents metal wiring reflection and RGB color mixing.
Smart Images

Figure CN115348999B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an optical laminate suitable for encapsulating a light-emitting element of a self-luminous display device such as Mini / Micro LED. Background Art
[0002] In recent years, self-luminous display devices represented by Mini / Micro LED display devices (Mini / MicroLight Emitting Diode Display, mini / micro light-emitting diode display devices) have been designed as the next generation of display devices. Mini / Micro LED display devices use a substrate with a high density of multiple tiny LED light-emitting elements (LED chips) as a display panel as a basic structure. The LED chips are encapsulated with an encapsulation material and a covering member such as a resin film and a glass plate is laminated on the outermost layer.
[0003] Mini / Micro LED display devices and other self-luminous display devices have several modes, such as white backlight mode, white light-emitting color filter mode, RGB mode, etc. In the white light-emitting color filter mode and RGB mode, in order to prevent the reflection of metal wiring, metal oxides such as ITO, etc. configured on the substrate of the display panel, black packaging materials are sometimes used (for example, see patent documents 1 to 3). Among them, in the RGB mode Mini / Micro LED display device with LED chips arranged, the above-mentioned black packaging material can also help prevent RGB color mixing and improve contrast.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2019-204905
[0007] Patent Document 2: Japanese Patent Application Publication No. 2017-203810
[0008] Patent Document 3: Japanese Patent Application No. 2018-523854 Summary of the invention
[0009] Problem that the invention aims to solve
[0010] When the aforementioned black packaging material is used, the upper part (image display side) of the light-emitting element such as the LED chip is covered by the black packaging material with reduced transmittance to visible light, so there is a problem of reduced luminous efficiency and darkened image. In order to cope with this problem, when the output power of the LED chip is increased to increase the luminous brightness, there is also a problem of increased power consumption.
[0011] In the case where the transmittance of the black encapsulation material to visible light is increased in order to improve the luminous efficiency, there is a trade-off relationship such that the antireflection function of the metal wiring and the like, the prevention of color mixing of RGB, and the contrast are reduced, and it is a difficult problem to balance them.
[0012] On the other hand, as the aforementioned black encapsulation material, a liquid curable resin or an adhesive containing a black colorant (dye, pigment) is being used. In the case of using a liquid curable resin containing a black colorant, there is a problem that the blackness is uneven due to uneven thickness.
[0013] The present invention has been conceived based on the above circumstances, and an object of the present invention is to provide an optical laminate suitable for manufacturing a self-luminous display device such as a Mini / Micro LED display device that improves the antireflection function and contrast of metal wiring and the like while improving the luminous efficiency.
[0014] Means for Solving the Problem
[0015] The inventors of the present invention conducted in-depth research in order to achieve the above object, and as a result, found that by using an optical laminate in which two adhesive layers having different transmittances are laminated with a substrate layer for manufacturing a self-luminous display device, it is possible to manufacture a self-luminous display device that combines improved luminous efficiency, improved antireflection function of metal wiring and the like, and contrast. The present invention has been completed based on these findings.
[0016] That is, a first aspect of the present invention provides an optical laminate having a laminated structure in which a first adhesive layer, a substrate, and a second adhesive layer are laminated in this order, and the visible light transmittance T1 of the first adhesive layer and the visible light transmittance T2 of the second adhesive layer satisfy T1 < T2.
[0017] In the optical laminate of the first aspect of the present invention, the aspect in which the visible light transmittance T1 of the first adhesive layer and the visible light transmittance T2 of the second adhesive layer satisfy T1 < T2, that is, the visible light transmittance of the first adhesive layer is lower than that of the second adhesive layer, is preferable in the following aspects: By using the optical laminate of the first aspect of the present invention for manufacturing a self-luminous display device, the first adhesive layer prevents reflection caused by metal wiring and the like on the display panel, prevents color mixing between the arranged light-emitting elements, and improves the contrast. In addition, this aspect is suitable in the following aspect: A configuration in which the second adhesive layer having a higher visible light transmittance than the first adhesive layer is located above the light-emitting element (image display side) can improve the luminous efficiency, brighten the image, and reduce power consumption caused by increasing the output power in order to increase the luminous brightness.
[0018] That is, by having this configuration, the optical laminate of the first aspect of the present invention improves the luminous efficiency while also solving the problems of antireflection function of metal wirings and the like, prevention of color mixing of RGB, and improvement of contrast, which are in a trade-off relationship therewith.
[0019] In the optical laminate of the first aspect of the present invention, preferably, the visible light transmittance T1 of the aforementioned first adhesive layer and the visible light transmittance T of the aforementioned substrate S satisfy T1 < T S . This solution is suitable in the following aspect: in the configuration where the substrate showing a higher visible light transmittance than the aforementioned first adhesive layer is located above (image display side) the aforementioned light-emitting element, it is possible to improve the luminous efficiency, make the image brighter, and reduce the power consumption caused by increasing the output power to improve the luminous brightness.
[0020] In the optical laminate of the first aspect of the present invention, preferably, the visible light transmittance T1 of the aforementioned first adhesive layer is 80% or less. This solution is suitable for further improving the antireflection function of metal wirings and the like, prevention of color mixing of RGB, and contrast. In addition, preferably, the visible light transmittance T2 of the aforementioned second adhesive layer is 85 to 100%. This solution is suitable for further improving the above-mentioned luminous efficiency. That is, the visible light transmittance T1 of the aforementioned first adhesive layer being 80% or less and the visible light transmittance T2 of the aforementioned second adhesive layer being 85 to 100% are extremely suitable in the following aspect: while improving the luminous efficiency, it is possible to take into account the antireflection function of metal wirings and the like, prevention of color mixing of RGB, and improvement of contrast, which are in a trade-off relationship therewith.
[0021] In the optical laminate of the first aspect of the present invention, preferably, the aforementioned first adhesive layer and the aforementioned second adhesive layer are adhesive layers formed of an adhesive composition selected from a photocurable adhesive composition and a solvent-based adhesive composition. Preferably, the adhesive composition forming the aforementioned first adhesive layer contains a colorant. These solutions are suitable in the following aspect: forming the solution where the aforementioned T1 and the aforementioned T2 satisfy T1 < T2, and further improving the above-mentioned luminous efficiency, antireflection function of metal wirings and the like, prevention of color mixing of RGB, and contrast.
[0022] In addition, in the case where the adhesive composition forming the aforementioned first adhesive layer contains a colorant, the solution where the aforementioned substrate is laminated between the aforementioned first adhesive layer and the second adhesive layer is preferable in the following aspect: preventing the colorant (especially dye) contained in the aforementioned first adhesive layer from moving to the aforementioned second adhesive layer and reducing the visible light transmittance of the second adhesive layer and the aforementioned luminous efficiency.
[0023] In the optical laminate of the first aspect of the present invention, it is preferred that the aforementioned adhesive composition contains an acrylic polymer. It is preferred that the aforementioned acrylic polymer contains a (meth) acrylic block copolymer. It is preferred that the adhesive composition forming the aforementioned first adhesive layer is a solvent-based adhesive composition containing a (meth) acrylic block copolymer. These schemes are preferred in the following aspects: when the optical laminate of the first aspect of the present invention is used for the manufacture of a self-luminous display device, the aforementioned first adhesive layer is seamlessly filled in the height difference of the light-emitting elements arranged on the display panel, and the height difference absorption is excellent and the processability is also excellent.
[0024] In the optical laminate of the first aspect of the present invention, the thickness of the first adhesive layer is preferably 10 to 300 μm, more preferably 15 to 200 μm. The thickness of the second adhesive layer is preferably 1 to 500 μm, more preferably 10 to 300 μm, and further preferably 15 to 200 μm. The ratio of the thickness of the second adhesive layer to the thickness of the first adhesive layer (the thickness of the second adhesive layer / the thickness of the first adhesive layer) is preferably 1.0 to 5.0, more preferably 1.2 to 4.0, and further preferably 1.3 to 3.0. These schemes are preferred in the following aspects: by fully encapsulating the light-emitting elements arranged on the display panel of the self-luminous display device with the first adhesive layer, reflection of metal wiring, etc., and mixing of RGB are prevented, and contrast is improved, and by covering the upper part (image display side) of the light-emitting element with the second adhesive layer having high transmittance, the luminous efficiency can be improved.
[0025] Preferably, the surface of the second adhesive layer not laminated with the substrate is further laminated with a second substrate. According to this scheme, the first adhesive layer constitutes a sealing material for sealing the light-emitting elements arranged on the display panel, and the second substrate constitutes a covering member of the outermost layer, so there is no need to laminate a covering member after sealing, which can reduce the number of processes and necessary components, and improve manufacturing efficiency.
[0026] In the optical laminate of the first aspect of the present invention, it is preferred that the surface of the second substrate on which the second adhesive layer is not laminated is subjected to an anti-reflection treatment and / or an anti-glare treatment. Preferably, the anti-reflection treatment and / or the anti-glare treatment is an anti-glare layer provided on a single surface of the second substrate. Preferably, the anti-glare layer is formed using an anti-glare layer forming material comprising a resin, particles and a thixotropy imparting agent, and the anti-glare layer is aggregated by the particles and the thixotropy imparting agent, so that the surface of the anti-glare layer has an aggregated portion forming a convex portion. Preferably, in the convex portion on the surface of the anti-glare layer, the average inclination angle θa (°) is in the range of 0.1 to 5.0. These schemes are preferred in the following aspects: imparting an anti-reflection function and / or an anti-glare function to the surface of the optical laminate of the first aspect of the present invention, preventing a reduction in visibility caused by reflection of external light, image reflection, etc., and adjusting aesthetics such as glossiness.
[0027] The optical laminate of the first aspect of the present invention may further include a surface protection film laminated on the surface of the second substrate not laminated with the second adhesive layer. This is suitable for preventing damage and dirt from attaching to the optical laminate or optical products including the optical laminate during manufacture, transportation, and shipment.
[0028] In addition, the second aspect of the present invention provides a self-luminous display device, the self-luminous display device comprising: a display panel having a plurality of light-emitting elements arranged on a single surface of a substrate, and an optical laminate of the first aspect of the present invention, wherein the surface of the display panel having the light-emitting elements arranged thereon is laminated with the first adhesive layer of the optical laminate. In the self-luminous display device of the second aspect of the present invention, the display panel may be an LED panel having a plurality of LED chips arranged on a single surface of a substrate. This scheme is preferred in the following aspects: the self-luminous display device of the second aspect of the present invention can prevent reflection of metal wiring on the substrate, prevent RGB color mixing, and improve contrast while improving luminous efficiency.
[0029] Effects of the Invention
[0030] By using the optical laminate of the present invention in the production of a self-luminous display device, a self-luminous display device with improved luminous efficiency, anti-reflection function of metal wiring etc., and contrast can be efficiently produced. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a schematic diagram (cross-sectional view) showing one embodiment of the optical layered body of the present invention.
[0032] Figure 2 It is a schematic diagram (cross-sectional view) showing another embodiment of the optical layered body of the present invention.
[0033] Figure 3 This is a schematic diagram (cross-sectional view) showing another embodiment of the optical laminate of the present invention.
[0034] Figure 4 This is a schematic diagram (cross-sectional view) showing another embodiment of the optical laminate of the present invention.
[0035] Figure 5 This is a schematic diagram (cross-sectional view) showing one embodiment of the self-luminous display device (Mini / Micro LED display device) of the present invention.
[0036] Figure 6 This is a schematic diagram (cross-sectional view) showing another embodiment of the self-luminous display device (Mini / Micro LED display device) of the present invention.
[0037] Figure 7 This is a schematic diagram (cross-sectional view) showing another embodiment of the self-luminous display device (Mini / Micro LED display device) of the present invention. Detailed Embodiments
[0038] The first aspect of the present invention provides an optical laminate. The optical laminate of the first aspect of the present invention has a laminated structure in which a first adhesive layer, a substrate (sometimes referred to as "first substrate" in this specification), and a second adhesive layer are laminated in sequence. The visible light transmittance T1 of the aforementioned first adhesive layer and the visible light transmittance T2 of the aforementioned second adhesive layer satisfy T1 < T2.
[0039] "Optical" in the optical laminate of the first aspect of the present invention means being used in optical applications, and more specifically, means being used in the manufacture of products (optical products) using optical components. As optical products, for example, image display devices, input devices such as touchscreens, etc. can be cited. Preferably, self-luminous display devices such as Mini / Micro LED display devices and organic EL (electroluminescence) display devices, and in particular, it can be suitably used for manufacturing Mini / Micro LED display devices.
[0040] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings, but the present invention is not limited thereto and is merely illustrative.
[0041] Figures 1 to 4 This is a schematic diagram (cross-sectional view) showing one embodiment of the optical laminate of the first aspect of the present invention. Figures 5 to 7 This is a schematic diagram (cross-sectional view) showing one embodiment of the self-luminous display device (Mini / Micro LED display device) of the second aspect of the present invention.
[0042] In Figure 1In [the structure], the optical laminate 10 has a laminated structure in which a first adhesive layer 1, a first substrate S, and a second adhesive layer 2 are laminated in this order.
[0043] In the present embodiment, the visible light transmittance T1 of the first adhesive layer 1 and the visible light transmittance T2 of the second adhesive layer 2 satisfy T1 < T2. That is, the visible light transmittance of the first adhesive layer 1 is lower than that of the second adhesive layer 2.
[0044] In the optical laminate 10 of the present embodiment, the first substrate S is laminated between the first adhesive layer 1 and the second adhesive layer 2. According to this configuration, the first substrate S physically isolates the first adhesive layer 1 and the second adhesive layer 2. For example, when the first adhesive layer 1 contains a colorant (especially a dye) as described later, it is possible to prevent the colorant from moving to the second adhesive layer 2 and reducing the transmittance.
[0045] In the present embodiment, preferably, the visible light transmittance T1 of the first adhesive layer 1 and the visible light transmittance T S of the first substrate S satisfy T1 < T S . That is, preferably, the visible light transmittance of the first substrate S is higher than that of the first adhesive layer 1. By making the visible light transmittance of the first substrate S higher than that of the first adhesive layer 1, sufficient transmittance is obtained in the visible light region. Since the first substrate S with higher transmittance is located above each LED chip 7 (the display image side), the absorption of visible light emitted from each LED chip 7 can be suppressed to a low level, improving the luminous efficiency, and thus the image can be made brighter.
[0046] In Figure 2 , a second substrate 3 is further laminated on the surface 2a of the second adhesive layer 2 of the optical laminate 10 where the first substrate S is not laminated. In Figure 3 , an antireflection treatment and / or an antiglare treatment 4 is performed on the surface 3a of the second substrate 3 in the optical laminate 20 where the second adhesive layer 2 is not laminated. In Figure 4 , an antiglare layer 4a is formed as an antireflection treatment and / or an antiglare treatment on the surface 3a in the optical laminate 20.
[0047] In Figure 5 , a self-luminous display device (Mini / Micro LED display device) 30 includes a display panel in which a plurality of LED chips 7 are arranged on one side of a substrate 5, and the optical laminate 20 of the first aspect of the present invention. The surface of the display panel on which the LED chips 7 are arranged is laminated with the first adhesive layer 1 of the optical laminate 20. In Figure 6In the self-luminous display device (Mini / Micro LED display device) 31, the surface 3a in the self-luminous display device (Mini / Micro LED display device) 30 is subjected to anti-reflection treatment and / or anti-glare treatment 4. Figure 7 In the self-luminous display device (Mini / Micro LED display device) 32, the surface 3a in the self-luminous display device (Mini / Micro LED display device) 30 is formed with an anti-glare layer 4a as an anti-reflection treatment and / or anti-glare treatment.
[0048] In this embodiment, a metal wiring layer 6 for sending a light control signal to each LED chip 7 is stacked on the substrate 5 of the display panel. Each LED chip 7 that emits light of each color of red (R), green (G), and blue (B) is alternately arranged on the substrate 5 of the display panel via the metal wiring layer 6. The metal wiring layer 6 is formed of a metal such as copper, which reflects the light emitted by each LED chip 7, reducing the image recognition. In addition, the light emitted by each LED chip 7 of each color of RGB will be mixed, and the contrast will be reduced.
[0049] In the present embodiment, each LED chip 7 arranged on the display panel is sealed without gaps by the first adhesive layer 1. That is, the first adhesive layer 1 can constitute a sealing material for each LED chip 7.
[0050] In this embodiment, the first adhesive layer 1 encapsulates the LED chips 7 arranged on the display panel and the metal wiring layer 6. By making the visible light transmittance of the first adhesive layer 1 lower than the visible light transmittance of the second adhesive layer 2, sufficient light shielding is achieved in the visible light region. Since the first adhesive layer 1 with higher light shielding performance encapsulates the LED chips 7 without gaps, it is possible to prevent color mixing between the LED chips 7 and improve contrast. In addition, since the first adhesive layer 1 with higher light shielding performance also encapsulates the surface of the metal wiring layer 6, it is possible to prevent reflection caused by the metal wiring layer 6.
[0051] In this embodiment, the second adhesive layer 2 is laminated on the upper part (display image side) of each LED chip 7 arranged on the display panel through the first substrate S, and functions as an interlayer filling material for bonding the second substrate 3. By making the visible light transmittance of the second adhesive layer 2 higher than the visible light transmittance of the first adhesive layer 1, it has sufficient transmittance in the visible light region. Since the second adhesive layer 2 with higher transmittance is located on the upper part (display image side) of each LED chip 7, the absorption of visible light emitted by each LED chip 7 can be suppressed to a lower level, the luminous efficiency is improved, and the image can be made brighter. In addition, since there is no need to increase the output power to increase the luminous brightness, the power consumption can be suppressed to a lower level.
[0052] The Mini / Micro LED display devices 30 to 32 of the present embodiment can be manufactured by laminating a display panel having a plurality of LED chips 7 arranged on a single surface of a substrate 5 to the first adhesive layer of the optical laminate 20 to 22 of the present embodiment. In this case, the second substrate 3 can constitute a covering member forming the outermost layer of the self-luminous display device (Mini / Micro LED display device). Therefore, according to the present embodiment, the process of separately installing the covering member can be omitted, the number of necessary components and processes can be reduced, and the production efficiency can be improved.
[0053] In addition, in the Mini / Micro LED display device 31 of the present embodiment, the surface 3a of the second substrate 3 is subjected to an anti-reflection treatment and / or an anti-glare treatment 4, and in the Mini / Micro LED display device 32, an anti-glare layer 4a is formed on the surface 3a of the second substrate 3 as an anti-glare treatment. The anti-reflection treatment and / or the anti-glare treatment 4, in particular the anti-glare layer 4a, prevents the surface 3a of the second substrate 3 as a covering member from being reduced in visibility due to reflection of external light, image reflection, etc., and / or adjusts aesthetics such as glossiness.
[0054] Hereinafter, each configuration will be described in detail.
[0055] <First Base Material>
[0056] In the present embodiment, there is no particular limitation on the first substrate S, and examples thereof include glass, transparent plastic film substrates, and the like. There is no particular limitation on the aforementioned transparent plastic film substrate, and preferably a substrate having excellent visible light transmittance and excellent transparency (preferably a substrate having a haze value of less than 5%) is preferred, and examples thereof include the transparent plastic film substrates described in Japanese Patent Gazette No. 2008-90263. As the aforementioned transparent plastic film substrate, a substrate having less optical birefringence can be suitably used. In the present embodiment, the first substrate S can also be used, for example, as a constituent optical component of a self-luminous display device, in which case, as the aforementioned transparent plastic film substrate, a film formed of triacetyl cellulose (TAC), polyester (e.g., polyethylene terephthalate, polyethylene naphthalate, etc.), polycarbonate, acrylic polymer, polyolefin having a cyclic or even norbornene structure, and the like is preferred.
[0057] In the optical laminate of the present embodiment, it is preferable that the visible light transmittance T1 of the first pressure-sensitive adhesive layer 1 and the visible light transmittance T2 of the first substrate S are equal to or greater than 0.05. S Meet T1 <T S. This solution is suitable in the following aspects: forming a structure in which the first substrate S showing a higher visible light transmittance than the first adhesive layer 1 is located on the upper part (image display side) of the aforementioned light-emitting element, which can improve the luminous efficiency, make the image bright, and reduce the power consumption caused by increasing the output power to increase the luminous brightness. The visible light transmittance T3 of the first substrate S is not particularly limited, for example, it is 85 to 100%, and can be 88% or more, 90% or more, or 92% or more.
[0058] In this embodiment, the thickness of the first substrate S is not particularly limited, and is preferably in the range of 10 to 500 μm, more preferably in the range of 20 to 300 μm, and most preferably in the range of 30 to 200 μm, taking into account strength, workability such as operability, and thinness. The refractive index of the first substrate S is not particularly limited, and is, for example, in the range of 1.30 to 1.80, and preferably in the range of 1.40 to 1.70.
[0059] <Second Base Material>
[0060] In the present embodiment, there is no particular restriction on the second substrate 3, and for example, glass, transparent plastic film substrates, etc. can be cited. There is no particular restriction on the aforementioned transparent plastic film substrate, and preferably a substrate with excellent visible light transmittance and excellent transparency (preferably a substrate with a haze value of less than 5%) can be cited. For example, a transparent plastic film substrate described in Japanese Patent Gazette No. 2008-90263 can be cited. As the aforementioned transparent plastic film substrate, a substrate with less optical birefringence can be appropriately used. In the present embodiment, the second substrate 3 can also be used as a covering member of a self-luminous display device, for example. In this case, as the aforementioned transparent plastic film substrate, a film formed by triacetyl cellulose (TAC), polycarbonate, acrylic polymer, polyolefin having a cyclic or norbornene structure, etc. is preferably used. In addition, in the present embodiment, the second substrate 3 can be the aforementioned covering member itself. If this scheme is used, the process of stacking the covering member separately can be reduced in the manufacture of the self-luminous display device, thereby reducing the number of processes and necessary components, and improving production efficiency can be achieved. In addition, if this scheme is used, the aforementioned covering member can be further thinned. It should be noted that, when the second base material 3 is a covering member, the surface 3 a constitutes the outermost surface of the self-luminous display device.
[0061] In the optical laminate of the present embodiment, it is preferable that the visible light transmittance T1 of the first adhesive layer 1 and the visible light transmittance T3 of the second substrate 3 satisfy T1 < T3. This solution is suitable in the following aspects: forming a configuration in which the second substrate 3 having a higher visible light transmittance than the first adhesive layer 1 is located above the light-emitting element (image display side), which can improve the luminous efficiency, make the image brighter, and can reduce the power consumption caused by increasing the output power to improve the luminous brightness. The visible light transmittance T3 of the second substrate 3 is not particularly limited, for example, it is 85 to 100%, and can be 88% or more, 90% or more, or 92% or more.
[0062] In the present embodiment, the thickness of the second substrate 3 is not particularly limited. For example, when considering workability such as strength and operability, and thin layer properties, etc., it is preferably in the range of 10 to 500 μm, more preferably in the range of 20 to 300 μm, and most preferably in the range of 30 to 200 μm. The refractive index of the second substrate 3 is not particularly limited, for example, it is in the range of 1.30 to 1.80, and preferably in the range of 1.40 to 1.70.
[0063] In the present embodiment, it is preferable that the surface 3a of the second substrate 3 is subjected to a reflective surface treatment and / or an antiglare treatment 4. When the surface 3a of the second substrate 3 is subjected to a reflective surface treatment and / or an antiglare treatment 4, this surface 3a constitutes the outermost surface of the self-luminous display device, which can prevent a decrease in visibility caused by reflection of external light, image reflection, etc., or adjust the aesthetics such as glossiness. An antiglare treatment that is easy to manufacture and has a low cost is preferred.
[0064] As the antireflection treatment, a known antireflection treatment can be used without particular limitation. For example, an antireflection (AR) treatment can be cited.
[0065] As the antireflection (AR) treatment, a known AR treatment can be applied without particular limitation. Specifically, it can be implemented by forming an antireflection layer (AR layer) obtained by laminating two or more optical thin films or the optical thin films with strictly controlled thickness and refractive index on one surface 3a of the second substrate 3. The AR layer exhibits an antireflection function by using the interference effect of light to cancel out the reversed phases of the incident light and the reflected light. The wavelength region of visible light that exhibits the antireflection function is, for example, 380 to 780 nm, and particularly the wavelength region with high visibility is in the range of 450 to 650 nm. The AR layer is preferably designed so that the reflectance at the center wavelength of 550 nm is minimized.
[0066] As the aforementioned AR layer, a multilayer antireflection layer having a structure of stacking two or five optical thin layers (thin films with strictly controlled thickness and refractive index) can be generally cited. By forming multiple layers with components having different refractive indices at a predetermined thickness, the freedom of optical design of the AR layer is increased, the antireflection effect can be further improved, and the spectral reflection characteristics can be made uniform (flat) in the visible light region. In the aforementioned optical thin film, since high thickness accuracy is required, the formation of each layer is generally implemented by vacuum evaporation, sputtering, CVD, etc., which belong to dry methods.
[0067] As the anti-glare (AG) treatment, a known AG treatment can be applied without particular limitation, and can be implemented, for example, by forming an anti-glare layer 4a on the surface 3a of the second substrate 3. As the anti-glare layer 4a, a known anti-glare layer can be adopted without limitation, and is generally formed as a layer in which inorganic or organic particles as an anti-glare agent are dispersed in a resin.
[0068] In this embodiment, the anti-glare layer 4a is formed using an anti-glare layer forming material including a resin, particles, and a thixotropy imparting agent, and the particles and the thixotropy imparting agent are aggregated to form a convex portion on the surface of the anti-glare layer 4a. According to this scheme, the anti-glare layer 4a has excellent display characteristics that take into account both anti-glare properties and prevention of white blur, and although the anti-glare layer is formed by the aggregation of particles, the generation of protrusions on the surface of the anti-glare layer that become appearance defects can be prevented, thereby improving the yield rate of the product.
[0069] Examples of the resin include thermosetting resins and ionizing radiation curable resins that are cured by ultraviolet rays or light. Commercially available thermosetting resins, ultraviolet curable resins, and the like may also be used as the resin.
[0070] As the aforementioned thermosetting resin and ultraviolet curing resin, for example, a curing compound having at least one of acrylate and methacrylate groups that is cured by heat, light (ultraviolet rays, etc.) or electron beams, for example, can be used, and examples thereof include oligomers or prepolymers such as acrylates and methacrylates of multifunctional compounds such as silicone resins, polyester resins, polyether resins, epoxy resins, urethane resins, alkyd resins, spiroacetal resins, polybutadiene resins, polythiol polyene resins, and polyols. These can be used alone or in combination of two or more.
[0071] In the aforementioned resin, for example, a reactive diluent having at least one of an acrylate group and a methacrylate group can also be used. The aforementioned reactive diluent can be, for example, a reactive diluent recorded in Japanese Patent Publication No. 2008-88309, including, for example, monofunctional acrylates, monofunctional methacrylates, multifunctional acrylates, multifunctional methacrylates, etc. As the aforementioned reactive diluent, preferred are acrylates with more than three functions and methacrylates with more than three functions. This is because the hardness of the anti-glare layer 4a can be made excellent. As the aforementioned reactive diluent, for example, butanediol glycerol ether diacrylate, acrylates of isocyanuric acid, methacrylates of isocyanuric acid, etc. can also be listed. These can be used alone or in combination of two or more.
[0072] The particles used to form the anti-glare layer 4a are used to give anti-glare properties and control the haze value of the anti-glare layer 4a as the main function so that the surface of the formed anti-glare layer 4a is concave-convex. The haze value of the anti-glare layer 4a can be designed by controlling the refractive index difference between the aforementioned particles and the aforementioned resin. As the aforementioned particles, for example, there are inorganic particles and organic particles. There is no particular restriction on the aforementioned inorganic particles, for example, silicon oxide particles, titanium oxide particles, aluminum oxide particles, zinc oxide particles, tin oxide particles, calcium carbonate particles, barium sulfate particles, talc particles, kaolin particles, calcium sulfate particles, etc. In addition, there is no particular restriction on the aforementioned organic particles, for example, polymethyl methacrylate resin powder (PMMA particles), silicone resin powder, polystyrene resin powder, polycarbonate resin powder, acrylic styrene resin powder, benzoguanamine resin powder, melamine resin powder, polyolefin resin powder, polyester resin powder, polyamide resin powder, polyimide resin powder, polyvinyl fluoride resin powder, etc. These inorganic particles and organic particles may be used alone or in combination of two or more.
[0073] The weight average particle size (D) of the aforementioned particles is preferably in the range of 2.5 to 10 μm. By making the weight average particle size of the aforementioned particles in the aforementioned range, for example, the anti-glare property is better and white blur can be prevented. The weight average particle size of the aforementioned particles is more preferably in the range of 3 to 7 μm. It should be noted that the weight average particle size of the aforementioned particles can be measured, for example, using the Coulter counting method. For example, by using a particle size distribution measuring device using the pore resistance method (trade name: Coulter particle size analyzer, manufactured by Beckman Coulter, Inc.), the resistance of the electrolyte equivalent to the volume of the particles when the particles pass through the aforementioned pores is measured, thereby measuring the number and volume of the aforementioned particles and calculating the weight average particle size.
[0074] There is no particular limitation on the shape of the particles, and they may be, for example, roughly spherical beads or amorphous particles such as powders. They are preferably roughly spherical particles, more preferably roughly spherical particles with an aspect ratio of less than 1.5, and most preferably spherical particles.
[0075] The ratio of the particles in the anti-glare layer 4a is preferably in the range of 0.2 to 12 parts by weight, more preferably in the range of 0.5 to 12 parts by weight, and further preferably in the range of 1 to 7 parts by weight relative to 100 parts by weight of the resin. By setting the ratio in the above range, for example, the anti-glare property is more excellent and white blur can be prevented.
[0076] Examples of the thixotropy-imparting agent for forming the anti-glare layer 4 a include organoclay, oxidized polyolefin, and modified urea.
[0077] In order to improve the affinity with the resin, the organoclay is preferably an organically treated clay. Examples of the organoclay include layered organoclay. The organoclay may be prepared by itself or a commercially available product may be used. Examples of the commercially available products include LUCENTITE SAN, LUCENTITE STN, LUCENTITE SEN, LUCENTITE SPN, SOMASIF ME-100, SOMASIF MAE, SOMASIF MTE, SOMASIF MEE, and SOMASIF MPE (trade names, all manufactured by Co-op Chemical Co., Ltd.); S-BEN, S-BEN C, S-BEN E, S-BEN W, S-BENP, S-BEN WX, S-BEN N-400, S-BEN NX, S-BEN NX80, S-BEN NO12S, S-BEN NEZ, S-BEN NO12, S-BEN NE, S-BEN NZ, and S-BEN NZ70; ORGANITE, ORGANITE D, and ORGANITE T (trade names, all manufactured by HOJUN Co., Ltd.); KUNIPIA F, KUNIPIA G, KUNIPIA G4 (trade names, all manufactured by KUNIMINE INDUSTRIES CO., LTD.); TIXOGEL VZ, CLAYTONE HT, CLAYTONE 40 (trade names, all manufactured by Rockwood Additives Ltd.), etc.
[0078] The oxidized polyolefin may be prepared by itself or a commercial product may be used. Examples of the commercial product include DISPARLON 4200-20 (trade name, manufactured by Kusumoto Chemicals Co., Ltd.) and FLOWNON SA300 (trade name, manufactured by Kyoeisha Chemical Co., Ltd.).
[0079] The modified urea is a reaction product of an isocyanate monomer or an adduct thereof with an organic amine. The modified urea may be prepared by itself or a commercial product may be used. Examples of the commercial product include BYK410 (manufactured by BYK Chemie).
[0080] The thixotropy-imparting agent may be used alone or in combination of two or more.
[0081] In the present embodiment, it is preferred that the height of the convex portion from the roughness average line of the anti-glare layer 4a is less than 0.4 times the thickness of the anti-glare layer 4a. More preferably, it is in the range of 0.01 times or more and less than 0.4 times, and more preferably in the range of 0.01 times or more and less than 0.3 times. If it is in this range, it is possible to appropriately prevent the formation of protrusions that become appearance defects on the convex portion. The anti-glare layer 4a of the present embodiment can make appearance defects less likely to occur by having a convex portion of such a height. Here, the height of the distance average line can be measured, for example, by the method described in Japanese Patent Publication No. 2017-138620.
[0082] The ratio of the thixotropy-imparting agent in the anti-glare layer 4 a is preferably in the range of 0.1 to 5 parts by weight, more preferably in the range of 0.2 to 4 parts by weight, based on 100 parts by weight of the resin.
[0083] There is no particular restriction on the thickness (d) of the anti-glare layer 4a, and it is preferably in the range of 3 to 12 μm. By making the thickness (d) of the anti-glare layer 4a in the aforementioned range, for example, the optical laminate 22 can be prevented from curling, and problems such as poor transportability and reduced productivity can be avoided. In addition, when the aforementioned thickness (d) is in the aforementioned range, the weight average particle size (D) of the aforementioned particles is preferably in the range of 2.5 to 10 μm as described above. By making the thickness (d) of the anti-glare layer 4a and the weight average particle size (D) of the aforementioned particles the aforementioned combination, the anti-glare property can be made more excellent. The thickness (d) of the anti-glare layer 4a is more preferably in the range of 3 to 8 μm.
[0084] The relationship between the thickness (d) of the anti-glare layer 4a and the weight average particle size (D) of the aforementioned particles is preferably within the range of 0.3≤D / d≤0.9. By being in this relationship, the anti-glare property is more excellent, and white blur can be prevented, thereby forming an anti-glare layer without appearance defects.
[0085] As described above, the optical laminate 22 of the present embodiment is agglomerated by the aforementioned particles and the aforementioned thixotropy imparting agent, thereby forming a convex portion on the surface of the anti-glare layer 4a. At the aggregation portion where the aforementioned convex portion is formed, the aforementioned particles exist in a state of being aggregated in the surface direction of the anti-glare layer 4a. Thus, the aforementioned convex portion forms a smooth shape. The anti-glare layer 4a of the present embodiment can prevent white blur while maintaining anti-glare properties by having a convex portion of such a shape, thereby making it difficult for appearance defects to occur.
[0086] The surface shape of the anti-glare layer 4a can be arbitrarily designed by controlling the aggregation state of the particles contained in the anti-glare layer forming material. The aggregation state of the aforementioned particles can be controlled, for example, by the material of the aforementioned particles (e.g., the chemical modification state of the particle surface, affinity for solvents, resins, etc.), the type and combination of resins (binders) or solvents, etc. Here, the present embodiment can control the aggregation state of the aforementioned particles by the thixotropy imparting agent contained in the aforementioned anti-glare layer forming material. As a result, the present embodiment can make the aggregation state of the aforementioned particles as described above, and can make the aforementioned convex portion form a smooth shape.
[0087] In the optical laminate 22 of the present embodiment, when the second substrate 3 is formed by a resin or the like, it is preferred to have a permeation layer at the interface between the second substrate 3 and the anti-glare layer 4a. The permeation layer is formed by the resin component contained in the material forming the anti-glare layer 4a penetrating into the second substrate 3. If a permeation layer is formed, the adhesion between the second substrate 3 and the anti-glare layer 4a can be improved, which is preferred. The thickness of the permeation layer is preferably in the range of 0.2 to 3 μm, and more preferably in the range of 0.5 to 2 μm. For example, when the second substrate 3 is triacetyl cellulose and the resin contained in the anti-glare layer 4a is an acrylic resin, the permeation layer can be formed. The permeation layer can be confirmed, for example, by observing the cross section of the optical laminate 22 with a transmission electron microscope (TEM), and the thickness can be measured.
[0088] Even when the present embodiment is applied to an optical laminate 22 having such a permeable layer, a desired smooth surface concavo-convex shape that takes into account both anti-glare properties and prevention of white blur can be easily formed. In the permeable layer, the more the second substrate 3 lacks adhesion to the anti-glare layer 4a, the more preferably it is formed thicker in order to improve adhesion.
[0089] In this embodiment, it is preferred that the number of appearance defects with a maximum diameter of 200 μm or more be 1 m in the anti-glare layer 4a. 2 The number of anti-glare layers 4a is 1 or less. It is more preferable that the aforementioned appearance defects are absent.
[0090] In the present embodiment, the second substrate 3 having the anti-glare layer 4a is preferably formed with a haze value in the range of 0 to 10%. The aforementioned haze value refers to the haze value (haze) according to JIS K 7136 (2000 edition). The aforementioned haze value is more preferably in the range of 0 to 5%, and further preferably in the range of 0 to 3%. In order to make the haze value in the above range, it is preferred to select the aforementioned particles and the aforementioned resin in such a manner that the refractive index difference between the aforementioned particles and the aforementioned resin is in the range of 0.001 to 0.02. By making the haze value in the above range, a clear image can be obtained, and the contrast in a dark place can also be improved.
[0091] In the present embodiment, it is preferred that the average inclination angle θa (°) at the concavo-convex shape on the surface of the anti-glare layer 4a is in the range of 0.1 to 5.0, more preferably in the range of 0.3 to 4.5, further preferably in the range of 1.0 to 4.0, and particularly preferably in the range of 1.6 to 4.0. Here, the average inclination angle θa is a value defined by the following mathematical formula (1). The average inclination angle θa is, for example, a value measured by the method described in Japanese Patent Application Laid-Open No. 2017-138620.
[0092] Average inclination angle θa = tan-1Δa (1)
[0093] In the above mathematical formula (1), Δa is a value obtained by dividing the sum of the differences (height h) between the apex of adjacent hills and the lowest point of valleys in the reference length L of the roughness curve specified in JIS B 0601 (1994 edition) by the above reference length L, as shown in the following mathematical formula (2). The above roughness curve is a curve obtained by removing the surface waviness component longer than the specified wavelength from the cross-sectional curve using a phase difference compensation type high-pass filter. In addition, the above cross-sectional curve refers to the contour that appears at the cut when the target surface is cut by a plane perpendicular to the target surface.
[0094] Δa=(h1+h2+h3…+hn) / L (2)
[0095] When θa is within the above range, the anti-glare property is more excellent and white blurring can be prevented.
[0096] When forming the anti-glare layer 4 a , the prepared anti-glare layer forming material (coating liquid) preferably exhibits thixotropy, and the Ti value specified below is preferably in the range of 1.3 to 3.5, and more preferably in the range of 1.3 to 2.8.
[0097] Ti value = β1 / β2
[0098] Here, β1 is the viscosity measured at a shear rate of 20 (1 / s) using RheoStress 6000 manufactured by HAAKE, and β2 is the viscosity measured at a shear rate of 200 (1 / s) using RheoStress 6000 manufactured by HAAKE.
[0099] If the Ti value is less than 1.3, appearance defects are likely to occur, and anti-glare properties and white blur properties are deteriorated. In addition, if the Ti value exceeds 3.5, the particles are less likely to aggregate and are more likely to be dispersed.
[0100] There is no particular limitation on the method for manufacturing the anti-glare layer 4a of the present embodiment, and any method may be used for manufacturing. For example, an anti-glare layer forming material (coating liquid) containing the aforementioned resin, the aforementioned particles, the aforementioned thixotropy imparting agent, and a solvent may be prepared, and the aforementioned anti-glare layer forming material (coating liquid) may be applied to the surface 3a of the aforementioned second substrate 3 to form a coating film, and the aforementioned coating film may be cured to form the anti-glare layer 4a, thereby manufacturing. In the present embodiment, a method of imparting a concave-convex shape by a transfer method based on a mold, sandblasting, an embossing roller, or the like may also be used in combination.
[0101] There is no particular limitation on the aforementioned solvent, and various solvents can be used, one alone or two or more in combination. The optimal solvent type and solvent ratio exist according to the composition of the aforementioned resin, the type and content of the aforementioned particles and the aforementioned thixotropy imparting agent. The solvent is not particularly limited, and examples thereof include: alcohols such as methanol, ethanol, isopropanol, butanol, and 2-methoxyethanol; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclopentanone; esters such as methyl acetate, ethyl acetate, and butyl acetate; ethers such as diisopropyl ether and propylene glycol monomethyl ether; glycols such as ethylene glycol and propylene glycol; cellosolves such as ethyl cellosolve and butyl cellosolve; aliphatic hydrocarbons such as hexane, heptane, and octane; aromatic hydrocarbons such as benzene, toluene, and xylene, and the like.
[0102] When the permeable layer is formed of triacetyl cellulose (TAC) as the second substrate 3, a good solvent for TAC can be preferably used. Examples of the solvent include ethyl acetate, methyl ethyl ketone, and cyclopentanone.
[0103] In addition, by appropriately selecting a solvent, the thixotropy of the anti-glare layer forming material (coating liquid) brought about by the thixotropy imparting agent can be well demonstrated. For example, when using an organoclay, toluene and xylene can be used alone or in combination, for example, when using an oxidized polyolefin, methyl ethyl ketone, ethyl acetate, propylene glycol monomethyl ether can be used alone or in combination, and for example, when using modified urea, butyl acetate and methyl isobutyl ketone can be used alone or in combination.
[0104] Various leveling agents can be added to the aforementioned anti-glare layer forming material. As the aforementioned leveling agent, for the purpose of preventing uneven coating (uniformization of the coating surface), for example, a fluorine-based or silicone-based leveling agent can be used. In the present embodiment, the leveling agent can be appropriately selected according to the situation where the surface of the anti-glare layer 4a is required to be anti-fouling, or the situation where an anti-reflection layer (low refractive index layer) or a layer containing an interlayer filler is to be formed on the anti-glare layer 4a. The present embodiment, for example, can make the coating liquid exhibit thixotropy by including the aforementioned thixotropy imparting agent, so uneven coating is not easily produced. Therefore, the present embodiment, for example, has the advantage of being able to expand the options of the aforementioned leveling agent.
[0105] The amount of the leveling agent blended is, for example, 5 parts by weight or less, and preferably in the range of 0.01 to 5 parts by weight, relative to 100 parts by weight of the resin.
[0106] The anti-glare layer forming material may be added with pigments, fillers, dispersants, plasticizers, ultraviolet absorbers, surfactants, antifouling agents, antioxidants, etc. as needed within a range that does not impair performance. These additives may be used alone or in combination of two or more.
[0107] For the anti-glare layer forming material, a conventionally known photopolymerization initiator as described in, for example, JP-A-2008-88309 can be used.
[0108] As a method for coating the anti-glare layer forming material on the surface 3 a of the second substrate 3 , for example, a coating method such as inkjet coating, die coating, spin coating, spray coating, gravure coating, roll coating, or rod coating can be used.
[0109] The anti-glare layer forming material is applied to the second substrate 3 to form a coating film, and the coating film is cured. The coating film is preferably dried before the curing. The drying may be, for example, natural drying, air drying, heating drying, or a combination of these methods.
[0110] There is no particular limitation on the curing method of the coating of the anti-glare layer forming material, but ultraviolet curing is preferred. The irradiation amount of the energy ray source is preferably 50 to 500 mJ / cm2 in terms of cumulative exposure at an ultraviolet wavelength of 365 nm. 2 If the irradiation dose is 50mJ / cm 2 If the curing temperature is 500 mJ / cm 2 The following can prevent the formed anti-glare layer from being colored.
[0111] As described above, an anti-glare layer 4a can be formed on the surface 3a of the second substrate 3. It should be noted that the anti-glare layer 4a can be formed by a manufacturing method other than the aforementioned method. Regarding the hardness of the anti-glare layer 4a of this embodiment, in the pencil hardness, although it is affected by the thickness of the layer, it is preferably 2H or more.
[0112] In this embodiment, the anti-glare layer 4a may be a multi-layer structure in which two or more layers are stacked.
[0113] In this embodiment, the AR layer (low refractive index layer) can be configured on the anti-glare layer 4a. For example, when the optical laminate 22 of this embodiment is installed in a self-luminous display device, one of the main factors that reduce the recognizability of the image can be listed as the reflection of light at the interface between the air and the anti-glare layer. The AR layer will reduce the surface reflection. It should be noted that the anti-glare layer 4a and the anti-reflection layer can be a multilayer structure with more than two layers stacked respectively.
[0114] In order to prevent the adhesion of contaminants and to improve the ease of removal of adhered contaminants, it is preferable to laminate an anti-contamination layer formed of a fluorine-containing silane compound or a fluorine-containing organic compound on the anti-glare layer 4 a .
[0115] In this embodiment, at least one of the second substrate 3 and the anti-glare layer 4a is preferably surface treated. If the surface of the second substrate 3 is surface treated, the adhesion with the anti-glare layer 4a is further improved. In addition, if the surface of the anti-glare layer 4a is surface treated, the adhesion with the aforementioned AR layer is further improved.
[0116] The other side of the anti-glare layer 4a may be subjected to solvent treatment to prevent the second substrate 3 from curling. In addition, a transparent resin layer may be formed on the other side of the anti-glare layer 4a to prevent the second substrate 3 from curling.
[0117] <Adhesive Layer>
[0118] In the present embodiment, the first adhesive layer 1 and the second adhesive layer 2 are adhesive layers formed of an adhesive composition selected from a photocurable adhesive composition and a solvent-based adhesive composition.
[0119] In this embodiment, the first adhesive layer 1 and the second adhesive layer 2 may both be adhesive layers formed of a photocurable adhesive composition, or both be adhesive layers formed of a solvent-based adhesive composition, or one may be an adhesive layer formed of a photocurable adhesive composition and the other may be an adhesive layer formed of a solvent-based adhesive composition.
[0120] In the present embodiment, in terms of excellent height difference absorbency and excellent processability, the first adhesive layer 1 is preferably an adhesive layer formed from a solvent-based adhesive composition. On the other hand, the second adhesive layer 2 may be an adhesive layer formed from a photocurable adhesive composition or may be an adhesive layer formed from a solvent-based adhesive composition.
[0121] The adhesive composition for forming the first adhesive layer 1 preferably contains a colorant. If the adhesive composition for forming the first adhesive layer 1 contains a colorant, it is preferable in terms of reducing the visible light transmittance of the first adhesive layer 1 and forming a solution where the aforementioned T1 and the aforementioned T2 satisfy T1 < T2. By encapsulating between the metal wiring layer 6 and the LED chip of the self-luminous display device (Mini / Micro LED display device) of the present embodiment with the first adhesive layer 1 having reduced visible light transmittance and imparted light-shielding properties, reflection caused by metal wiring etc. can be prevented, color mixing between LED chips can be prevented, and the contrast of the image can be improved.
[0122] The adhesive composition for forming the second adhesive layer 2 may contain a colorant, but from the perspective of forming a solution where the aforementioned T1 and the aforementioned T2 satisfy T1 < T2, it is preferably colorant-free.
[0123] <Photocurable adhesive composition>
[0124] The aforementioned photocurable adhesive composition contains a polymer, a photopolymerizable compound, and a photoinitiator. That is, the photocurable adhesive composition for forming the first adhesive layer 1 and the second adhesive layer 2 of the present embodiment contains a polymer, a photopolymerizable compound, and a photoinitiator.
[0125] The adhesive layer formed using the photocurable adhesive composition is roughly classified into: an adhesive layer of the type that undergoes photocuring (first method); and an adhesive layer of the type that does not undergo photocuring and undergoes photocuring after being bonded to the display panel described later (second method). The first adhesive layer 1 and the second adhesive layer 2 may both be adhesive layers of the first method, may both be adhesive layers of the second method, or may be an adhesive layer of the first method for one and an adhesive layer of the second method for the other.
[0126] [First method]
[0127] The adhesive layer of the first method can be formed by coating a photocurable adhesive composition containing a polymer, a photopolymerizable compound, and a photoinitiator on a release film and performing photocuring.
[0128] <Photocurable adhesive composition>
[0129] (Polymer)
[0130] Examples of the polymer contained in the photocurable adhesive composition include acrylic polymers, silicone polymers, polyesters, polyurethanes, polyamides, polyvinyl ethers, vinyl acetate / vinyl chloride copolymers, modified polyolefins, epoxies, fluorine polymers, natural rubbers, synthetic rubbers and other rubber-based polymers. In particular, acrylic polymers can be preferably used from the perspective of exhibiting appropriate adhesive properties such as wettability, cohesiveness and adhesion and also having excellent weather resistance, heat resistance and the like.
[0131] The acrylic polymer contains an alkyl (meth)acrylate as a main monomer component. It should be noted that in the present specification, "(meth)acrylic acid" refers to acrylic acid and / or methacrylic acid. The amount of the alkyl (meth)acrylate relative to the total amount of the monomer components constituting the acrylic polymer is preferably 50% by weight or more, more preferably 55% by weight or more, and even more preferably 60% by weight or more.
[0132] As the alkyl (meth)acrylate, there can be preferably used an alkyl (meth)acrylate having an alkyl group with a carbon number of 1 to 20. The alkyl group of the alkyl (meth)acrylate may have a branch or a cyclic alkyl group.
[0133] Specific examples of the (meth)acrylic acid alkyl ester having a chain alkyl group include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, propylene (meth)acrylate, octyl ... The preferred (meth)acrylate alkyl esters having a chain alkyl group for use in the first embodiment include butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octadecyl (meth)acrylate, and dodecyl (meth)acrylate. The amount of the (meth)acrylate alkyl ester having a chain alkyl group relative to the total amount of the monomer components constituting the acrylic polymer is, for example, about 40 to 90% by weight, and may be 45 to 80% by weight or 50 to 70% by weight.
[0134] Specific examples of alkyl (meth)acrylates having an alicyclic alkyl group include: cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, cyclooctyl (meth)acrylate, and other cyclopentyl (meth)acrylates; (meth)acrylates having a dicyclic aliphatic hydrocarbon ring such as isobornyl (meth)acrylate; (meth)acrylates having a tricyclic or higher aliphatic hydrocarbon ring such as dicyclopentyl (meth)acrylate, dicyclopentyloxyethyl (meth)acrylate, tricyclopentyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, and 2-ethyl-2-adamantyl (meth)acrylate. Preferred alkyl (meth)acrylates having an alicyclic alkyl group for use in the first embodiment include cyclohexyl (meth)acrylate and isobornyl (meth)acrylate. The amount of the alkyl (meth)acrylate having an alicyclic alkyl group is, for example, about 3 to 50% by weight, or 5 to 40% by weight or 10 to 30% by weight, based on the total amount of monomer components constituting the acrylic polymer.
[0135] The acrylic polymer may contain polar group-containing monomers such as hydroxyl-containing monomers, carboxyl-containing monomers, and nitrogen-containing monomers as constituent monomer components. By making the acrylic polymer contain polar group-containing monomers as constituent monomer components, there is a tendency for the cohesive force of the adhesive to be improved and the adhesive force to be improved. Preferred polar group-containing monomers for the first embodiment are hydroxyl-containing monomers and nitrogen-containing monomers. The amount of polar group-containing monomers (the sum of hydroxyl-containing monomers, carboxyl-containing monomers, and nitrogen-containing monomers) relative to the total amount of monomer components constituting the acrylic polymer is, for example, about 3 to 50% by weight, and can be 5 to 40% by weight or 10 to 30% by weight.
[0136] As hydroxyl-containing monomers, there can be cited (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (meth)acrylate (4-hydroxymethylcyclohexyl)-methyl ester. When a cross-linking structure is introduced into a polymer using an isocyanate cross-linking agent, a hydroxyl group can constitute a reaction site (cross-linking point) with an isocyanate group. As preferred hydroxyl-containing monomers for the first embodiment, there are 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate. The amount of the hydroxyl-containing monomer relative to the total amount of the monomer components constituting the acrylic polymer is, for example, about 3 to 50% by weight, and can be 5 to 40% by weight or 10 to 30% by weight.
[0137] As carboxyl-containing monomers, there can be listed: acrylic monomers such as (meth) acrylic acid, carboxyethyl (meth) acrylic acid, carboxypentyl (meth) acrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, etc. In the case of introducing a cross-linked structure into a polymer using an epoxy crosslinking agent, the carboxyl group can constitute a reaction site (crosslinking point) with an epoxy group. As a preferred carboxyl-containing monomer for the first embodiment, there is (meth) acrylic acid. The amount of the carboxyl-containing monomer relative to the total amount of the monomer components constituting the acrylic polymer is, for example, about 3 to 50% by weight, and can be 5 to 40% by weight or 10 to 30% by weight.
[0138] Examples of nitrogen-containing monomers include vinyl monomers such as N-vinylpyrrolidone, methylvinylpyrrolidone, vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, vinylmorpholine, (meth)acryloylmorpholine, N-vinylcarboxylic acid amides, N-vinylcaprolactam, and acrylamide, and cyano-containing monomers such as acrylonitrile and methacrylonitrile. As a preferred nitrogen-containing monomer for the first embodiment, there is N-vinylpyrrolidone. The amount of the nitrogen-containing monomer relative to the total amount of the monomer components constituting the acrylic polymer is, for example, about 3 to 50% by weight, and can be 5 to 40% by weight or 10 to 30% by weight.
[0139] Acrylic polymers may include, as monomer components other than the above (sometimes referred to as "other monomers"), acid anhydride group-containing monomers, caprolactone adducts of (meth)acrylic acid, sulfonic acid group-containing monomers, phosphoric acid group-containing monomers, vinyl acetate, vinyl propionate, styrene, α-methylstyrene and other vinyl monomers; epoxy group-containing monomers such as glycidyl (meth)acrylate; glycol acrylate monomers such as polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate; acrylate monomers such as tetrahydrofurfuryl (meth)acrylate, fluoro(meth)acrylate, silicone (meth)acrylate, 2-methoxyethyl (meth)acrylate, etc.
[0140] The glass transition temperature (Tg) of the polymer contained in the photocurable adhesive composition is preferably below 0°C. The glass transition temperature of the polymer may be below -5°C, below -10°C or below -15°C. The glass transition temperature of the polymer is the peak temperature of the loss tangent (tanδ) measured based on dynamic viscoelasticity. When a cross-linked structure is introduced into the polymer, the glass transition temperature can be calculated based on the theoretical Tg according to the composition of the polymer. The theoretical Tg is calculated using the Fox formula described later.
[0141] The polymer can be obtained by polymerizing the above-mentioned monomer components by various known methods. The polymerization method is not particularly limited, and it is preferred to prepare the polymer by photopolymerization. Photopolymerization can prepare the polymer without using a solvent, so when forming the adhesive layer, it is not necessary to dry and remove the solvent, and a thick adhesive layer can be uniformly formed.
[0142] In the preparation of the adhesive layer of the first mode, it is preferably prepared in the form of a polymer (prepolymer) with a low degree of polymerization in which a part of the monomer components are unreacted and remain. The composition for preparing the prepolymer (prepolymer forming composition) preferably also contains a photopolymerization initiator on the basis of the monomer. The photopolymerization initiator can be appropriately selected according to the type of monomer. For example, a light free radical polymerization initiator can be used for the polymerization of acrylic polymers. As the photopolymerization initiator, benzoin ether photopolymerization initiators, acetophenone photopolymerization initiators, α-ketol photopolymerization initiators, aromatic sulfonyl chloride photopolymerization initiators, photoactive oxime photopolymerization initiators, benzoin photopolymerization initiators, benzyl photopolymerization initiators, benzophenone photopolymerization initiators, ketal photopolymerization initiators, thioxanthone photopolymerization initiators, acylphosphine oxide photopolymerization initiators, etc. can be listed.
[0143] During polymerization, a chain transfer agent, a polymerization inhibitor (polymerization retardant), etc. may be used for the purpose of molecular weight adjustment, etc. Examples of the chain transfer agent include mercaptans such as α-thioglycerol, lauryl mercaptan, glycidyl mercaptan, thioglycolic acid, 2-mercaptoethanol, thioglycolic acid, 2-ethylhexyl thioglycolate, and 2,3-dimercapto-1-propanol, and α-methylstyrene dimer.
[0144] The polymerization rate of the prepolymer is not particularly limited, but is preferably 3 to 50% by weight, more preferably 5 to 40% by weight, from the perspective of forming a viscosity suitable for coating on a substrate. The polymerization rate of the prepolymer can be adjusted to a desired range by adjusting the type and amount of the photopolymerization initiator, the irradiation intensity / irradiation time of active light such as UV light, etc. The polymerization rate of the prepolymer is the non-volatile component when heated at 130°C for 3 hours, and is calculated using the following formula. The polymerization rate (non-volatile component) of the adhesive layer is also measured using the same method.
[0145] Polymerization rate (%) = weight after heating / weight before heating × 100
[0146] As mentioned above, the photocurable adhesive composition for forming the adhesive layer contains a polymer, a photopolymerizable compound and a photopolymerization initiator. For example, the photocurable adhesive composition can be obtained by adding a photopolymerizable compound and a photopolymerization initiator to a prepolymer. Alternatively, a low molecular weight polymer (oligomer) can be used instead of a prepolymer, and a photopolymerizable compound, a photopolymerization initiator and a colorant can be mixed into the low molecular weight polymer to prepare the photocurable adhesive composition.
[0147] (Photopolymerizable compound)
[0148] The photopolymerizable compound contained in the photocurable adhesive composition has one or more photopolymerizable functional groups in one molecule. The photopolymerizable functional group may be any of free radical polymerizable, cationic polymerizable and anionic polymerizable, and is preferably a free radical polymerizable functional group having an unsaturated double bond (ethylenically unsaturated group) from the perspective of excellent reactivity.
[0149] The prepolymer contains monomers that have not reacted with the polymer, and the unreacted monomers retain photopolymerizability. Therefore, in the preparation of the photocurable adhesive composition, it is not necessarily necessary to add a photopolymerizable compound. In the case of adding a photopolymerizable compound to the prepolymer, the added photopolymerizable compound may be the same as or different from the monomer used to prepare the prepolymer.
[0150] In the case where the polymer is an acrylic polymer, from the perspective of high compatibility with the polymer, the compound added as the photopolymerizable compound is preferably a monomer or oligomer having a (meth)acryloyl group as a photopolymerizable functional group. The photopolymerizable compound can be a polyfunctional compound having two or more photopolymerizable functional groups in one molecule. As the photopolymerizable polyfunctional compound, polyfunctional (meth)acrylates can be listed. As the polyfunctional (meth)acrylates, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, bisphenol A ethylene oxide modified di(meth)acrylate, bisphenol A propylene oxide modified di(meth)acrylate, alkanediol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, pentaerythritol di(meth)acrylate, neopentyl glycol di(meth)acrylate, glycerol di(meth)acrylate, urethane di(meth)acrylate can be listed. esters; trifunctional (meth)acrylates such as pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate and ethoxylated isocyanuric acid tri(meth)acrylate; tetrafunctional (meth)acrylates such as di(trimethylolpropane) tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate and pentaerythritol tetra(meth)acrylate; pentafunctional or higher (meth)acrylates such as dipentaerythritol penta(meth)acrylate and dipentaerythritol hexa(meth)acrylate.
[0151] When a multifunctional compound is used as a photopolymerizable compound, the amount of the multifunctional compound used is preferably 10 parts by weight or less, more preferably 0.001 to 1 part by weight, and further preferably 0.005 to 0.5 parts by weight, relative to 100 parts by weight of the polymer (including prepolymer). When the amount of the multifunctional monomer is too large, the adhesive layer after photocuring sometimes has low viscosity and poor adhesion. The amount of the multifunctional compound used is 10 parts by weight or less, and can be 5 parts by weight or less, 3 parts by weight or less, or 1 part by weight or less. The amount of the multifunctional monomer used can be 0, or can be more than 0.001 parts by weight, more than 0.01 parts by weight, or more than 0.1 parts by weight.
[0152] When a monomer that forms a prepolymer is used as a photopolymerizable compound, a hydroxyl-containing monomer is preferred, and 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are more preferred. When a hydroxyl-containing monomer is used as a photopolymerizable compound, the amount of the hydroxyl-containing monomer is preferably 40 parts by weight or less, more preferably 1 to 30 parts by weight, and further preferably 5 to 20 parts by weight, relative to 100 parts by weight of the polymer (including the prepolymer). The amount of the hydroxyl-containing monomer is 40 parts by weight or less, and can be 30 parts by weight or less, or 20 parts by weight or less. The amount of the hydroxyl-containing monomer can be 0, or can be 1 part by weight or more, 5 parts by weight or more, or 10 parts by weight or more.
[0153] (Photopolymerization Initiator)
[0154] The photocurable adhesive composition contains a photopolymerization initiator. The photopolymerization initiator generates free radicals, acids, bases, etc. by irradiating active light such as ultraviolet rays, and can be appropriately selected according to the type of photopolymerizable compound. When the photopolymerizable compound is a compound having a (meth)acryloyl group (for example, a monofunctional or polyfunctional (meth)acrylate), it is preferred to use a photoradical polymerization initiator as the photopolymerization initiator. The photopolymerization initiator can be used alone or in combination of two or more.
[0155] When the photopolymerization initiator used in the preparation (polymerization) of the aforementioned polymer (including prepolymer) remains without being deactivated, the addition of the photopolymerization initiator can be omitted. When a photopolymerization initiator is added to the polymer, the added photopolymerization initiator may be the same as or different from the photopolymerization initiator used to prepare the polymer.
[0156] The photopolymerization initiator included in the photocurable adhesive composition preferably has a maximum absorption in a wavelength region where the light absorption generated by the colorant described later is small. Specifically, the photopolymerization initiator preferably has a maximum absorption in a wavelength region of 330 to 400 nm. By making the photopolymerization initiator have a maximum absorption in a region where the light absorption generated by the colorant is small, the curing inhibition caused by the colorant can be suppressed, so the polymerization rate can be fully increased by photocuring. Examples of the photoradical polymerization initiator having a maximum absorption in a wavelength region of 330 to 400 nm include: hydroxy ketones, benzil dimethyl ketals, amino ketones, acyl phosphine oxides, benzophenones, trichloromethyl-containing triazine derivatives, and the like.
[0157] The content of the photopolymerization initiator in the photocurable adhesive composition is about 0.01 to 10 parts by weight, preferably about 0.05 to 5 parts by weight, based on 100 parts by weight of the total monomer amount (monomers for preparing the polymer and the photopolymerizable compound added to the polymer).
[0158] (Colorant)
[0159] The photocurable adhesive composition for the first mode may contain a colorant. In particular, the photocurable adhesive composition forming the first adhesive layer 1 preferably further contains a colorant. If the photocurable adhesive composition forming the first adhesive layer 1 contains a colorant, it is preferable in the following aspects: the transmittance of the first adhesive layer 1 to visible light is reduced, and a scheme in which the aforementioned T1 and the aforementioned T2 satisfy T1 < T2 is formed. By encapsulating between the metal wiring layer 6 and the LED chip of the self-luminous display device (Mini / Micro LED display device) of the present embodiment with the first adhesive layer 1 having reduced transmittance to visible light and imparted light-shielding properties, reflection caused by the metal wiring or the like can be prevented, color mixing between the LED chips can be prevented, and the contrast of the image can be improved.
[0160] The aforementioned colorant may be a dye or a pigment as long as it can be dissolved or dispersed in the photocurable adhesive composition. From the perspective that low haze can be achieved with a small amount of addition and it is easy to be uniformly distributed without sedimentation like a pigment, a dye is preferred. In addition, from the perspective of obtaining high color rendering with a small amount of addition, a pigment is also preferred. When a pigment is used as the colorant, a pigment with low conductivity or no conductivity is preferred. In addition, when a dye is used, it is preferably used in combination with an antioxidant or the like described later.
[0161] As the aforementioned colorant, there is no particular limitation, and a colorant that absorbs visible light and has ultraviolet transmittance is preferred. That is, the colorant preferably has an average transmittance at wavelengths of 330 to 400 nm greater than the average transmittance at wavelengths of 400 to 700 nm. In addition, the maximum value of the transmittance of the colorant at wavelengths of 330 to 400 nm is preferably greater than the maximum value of the transmittance at wavelengths of 400 to 700 nm. Regarding the transmittance of the colorant, a solution or dispersion obtained by diluting with an appropriate solvent such as tetrahydrofuran (THF) or a dispersion medium (an organic solvent with little absorption in the wavelength range of 330 to 700 nm) in such a way that the transmittance at a wavelength of 400 nm is about 50 to 60% is used for measurement.
[0162] Examples of the ultraviolet-transmitting black pigment with less ultraviolet absorption than visible light absorption include "9050BLACK", "UVBK-0001", etc. manufactured by TOKUSHIKI CO., Ltd. Examples of the ultraviolet-transmitting black dye include "SOC-L-0123" manufactured by ORIENT CHEMICAL INDUSTRIES CO., LTD.
[0163] Carbon black and titanium black, which are generally used as black colorants, absorb more ultraviolet light than visible light (ultraviolet transmittance is less than visible light transmittance). Therefore, if a colorant such as carbon black is added to a photocurable adhesive composition that is sensitive to ultraviolet light, most of the ultraviolet light irradiated for photocuring will be absorbed by the colorant, the amount of light absorbed by the photopolymerization initiator is small, and photocuring will take time (the cumulative amount of irradiated light increases). In addition, when the thickness of the adhesive layer is large, since there is less ultraviolet light reaching the surface on the opposite side of the light irradiation surface, there is a tendency that even with long-term light irradiation, photocuring is still insufficient. In contrast, by using a colorant with a higher transmittance of ultraviolet light than visible light, the curing inhibition caused by the colorant can be suppressed.
[0164] The content of the colorant in the photocurable adhesive composition forming the first adhesive layer is, for example, about 0.01 to 20 parts by weight relative to 100 parts by weight of the total monomer amount, and can be appropriately set according to the type of colorant, the color tone of the adhesive layer, the light transmittance, etc. The colorant can be added to the composition in the form of a solution or dispersion dissolved or dispersed in an appropriate solvent.
[0165] The photocurable adhesive composition forming the second adhesive layer preferably does not contain a colorant. By making the photocurable adhesive composition forming the second adhesive layer free of a colorant, the permeability to visible light is increased, and the luminous efficiency of the self-luminous display device (Mini / Micro LED display device) is improved. In the case where the photocurable adhesive composition forming the second adhesive layer includes a colorant, its content is, for example, about 0.1 parts by weight or less relative to 100 parts by weight of the total amount of monomers. In the case where a colorant is not mixed in the photocurable adhesive composition forming the second adhesive layer, there may also be a situation where the colorant mixed in the first adhesive layer moves to the second adhesive layer.
[0166] (Silane coupling agent)
[0167] The photocurable adhesive composition may contain a silane coupling agent within a range that does not impair the effects of the present invention. If the photocurable adhesive composition contains a silane coupling agent, the bonding reliability to glass (particularly the bonding reliability to glass under a high temperature and high humidity environment) is improved, which is preferred.
[0168] As the aforementioned silane coupling agent, there is no particular limitation, and preferably includes: γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-phenyl-aminopropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, etc. Among them, γ-glycidoxypropyltrimethoxysilane is preferred. In addition, as a commercial product, for example, the trade name "KBM-403" (manufactured by Shin-Etsu Chemical Co., Ltd.) can be listed. It should be noted that the silane coupling agent can be used alone or in combination of two or more.
[0169] The content of the silane coupling agent in the photocurable adhesive composition is not particularly limited, but is preferably 0.01 to 1 part by weight, more preferably 0.03 to 0.5 part by weight, based on 100 parts by weight of the polymer.
[0170] (Other ingredients)
[0171] In the first embodiment, the photocurable adhesive composition may include ingredients other than polymers, photopolymerizable compounds, photopolymerization initiators and colorants. For example, a chain transfer agent may be included for the purpose of adjusting the photocuring speed. In addition, oligomers and tackifiers may be included for the purpose of adjusting the viscosity of the aforementioned photocurable adhesive composition, adjusting the adhesion of the adhesive layer, etc. As an oligomer, for example, an oligomer with a weight average molecular weight of about 1000 to 30000 can be used. As an oligomer, acrylic oligomers are preferred from the perspective of excellent compatibility with acrylic polymers. The aforementioned photocurable adhesive composition may include additives such as plasticizers, softeners, anti-deterioration agents, fillers, antioxidants, surfactants, antistatic agents, etc.
[0172] [Second method]
[0173] The second embodiment of the adhesive layer is a type of adhesive layer that is not photocured, and is an adhesive layer obtained by forming a photocurable adhesive composition into a sheet. Since the second embodiment of the adhesive layer contains a photopolymerizable compound in an unreacted state, the adhesive layer has photocurability.
[0174] The photocurable adhesive composition for forming the adhesive layer of the second embodiment contains a polymer, a photopolymerizable compound, and a photopolymerization initiator.
[0175] (polymer)
[0176] As the polymer contained in the pressure-sensitive adhesive composition, various polymers can be applied as in the first embodiment, and an acrylic polymer can be preferably used. The monomer components constituting the acrylic polymer are the same as in the first embodiment.
[0177] In order to introduce a crosslinked structure using a crosslinking agent described later, it is preferred that a hydroxyl-containing monomer and / or a carboxyl-containing monomer be included in the monomer components constituting the polymer. For example, when an isocyanate crosslinking agent is used, a hydroxyl-containing monomer is preferably included as a monomer component. When an epoxy crosslinking agent is used, a carboxyl-containing monomer is preferably included as a monomer.
[0178] In the second embodiment, since photocuring is not performed on the substrate, a polymer with a relatively large molecular weight can be used as the polymer contained in the photocurable adhesive composition to form a solid (fixed shape) adhesive layer. The weight average molecular weight of the polymer is, for example, about 100,000 to 2,000,000.
[0179] Since the high molecular weight polymer is solid, the adhesive composition is preferably a solution of the polymer dissolved in an organic solvent. For example, a polymer solution can be obtained by solution polymerization of the monomer components. The polymer solution can be prepared by dissolving a solid polymer in an organic solvent.
[0180] As solvents for solution polymerization, ethyl acetate, toluene, etc. are generally used. The solution concentration is usually about 20 to 80% by weight. As polymerization initiators, thermal polymerization initiators such as azo initiators, peroxide initiators, and redox initiators obtained by combining peroxides and reducing agents (for example, a combination of persulfate and sodium bisulfite, a combination of peroxide and sodium ascorbate) are preferably used. There is no particular restriction on the amount of the polymerization initiator used, for example, it is preferably about 0.005 to 5 parts by weight, and more preferably about 0.02 to 3 parts by weight relative to 100 parts by weight of the total amount of monomer components forming the polymer.
[0181] (Photopolymerizable compound)
[0182] In the second embodiment, the photopolymerizable compound contained in the pressure-sensitive adhesive composition is the same as described above in the first embodiment, and a compound having one or two or more photopolymerizable functional groups can be used.
[0183] (Photopolymerization Initiator)
[0184] In the second embodiment, the photopolymerization initiator contained in the adhesive composition is the same as that described above for the first embodiment, and preferably has a maximum absorption in the wavelength range of 330 to 400 nm. The amount of the photopolymerization initiator is about 0.01 to 10 parts by weight, preferably about 0.05 to 5 parts by weight, relative to 100 parts by weight of the polymer.
[0185] (Colorant)
[0186] The adhesive composition used in the second mode may contain a colorant. In particular, the photocurable adhesive composition forming the first adhesive layer 1 preferably further contains a colorant. If the photocurable adhesive composition forming the first adhesive layer 1 contains a colorant, it is preferable in the following aspects: the transmittance of the first adhesive layer 1 to visible light is reduced, and a scheme where the aforementioned T1 and the aforementioned T2 satisfy T1 < T2 is formed. By encapsulating the metal wiring layer 6 and the LED chip of the self-luminous display device (Mini / Micro LED display device) of the present embodiment with the first adhesive layer 1 having reduced transmittance to visible light and imparted light-shielding properties, reflection caused by the metal wiring or the like can be prevented, color mixing between LED chips can be prevented, and the contrast of the image can be improved.
[0187] The colorant contained in the adhesive composition used in the second mode is the same as that described above for the first mode, and preferably has an average transmittance at wavelengths of 330 to 400 nm greater than the average transmittance at wavelengths of 400 to 700 nm. In addition, the colorant preferably has a maximum transmittance at wavelengths of 330 to 400 nm greater than the maximum transmittance at wavelengths of 400 to 700 nm.
[0188] (Crosslinking agent)
[0189] The adhesive composition of the second mode preferably contains a crosslinking agent capable of crosslinking with the above polymer. Specific examples of the crosslinking agent for introducing a crosslinked structure into the polymer include: isocyanate crosslinking agents, epoxy crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, carbodiimide crosslinking agents, metal chelate crosslinking agents, etc. Among them, from the perspective of high reactivity with the hydroxyl and carboxyl groups of the polymer and easy introduction of the crosslinked structure, isocyanate crosslinking agents and epoxy crosslinking agents are preferred. These crosslinking agents react with functional groups such as hydroxyl and carboxyl groups introduced into the polymer to form a crosslinked structure.
[0190] As the isocyanate crosslinking agent, a polyisocyanate having two or more isocyanate groups in one molecule can be used. Examples of the isocyanate crosslinking agent include lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, and isophorone diisocyanate; aromatic isocyanates such as 2,4-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, and xylylene diisocyanate; trimethylolpropane / toluene diisocyanate trimer adduct (e.g., "CORONATE L" manufactured by Tosoh Corporation), trimethylolpropane / hexamethylene diisocyanate trimer adduct (e.g., "CORONATE HL" manufactured by Tosoh Corporation), trimethylolpropane adduct of xylylene diisocyanate (e.g., "TAKENATE D110N" manufactured by Mitsui Chemicals, Inc.), isocyanurate of hexamethylene diisocyanate (e.g., "CORONATE 500N" manufactured by Tosoh Corporation), and isocyanurate of hexamethylene diisocyanate (e.g., "CORONATE 500N" manufactured by Tosoh Corporation). HX") and other isocyanate adducts.
[0191] As the epoxy crosslinking agent, a polyfunctional epoxy compound having two or more epoxy groups in one molecule can be used. The epoxy group of the epoxy crosslinking agent may be a glycidyl group. Examples of the epoxy crosslinking agent include N,N,N',N'-tetraglycidyl-m-xylene diamine, diglycidyl aniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, sorbitol polyglycidyl ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, adipic acid diglycidyl ester, phthalic acid diglycidyl ester, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, and bisphenol-S-diglycidyl ether. As the epoxy crosslinking agent, commercially available products such as "DENACOL" manufactured by Nagase ChemteX Corporation and "TETRAD X" and "TETRAD C" manufactured by Mitsubishi Gas Chemical Co., Ltd. can be used.
[0192] The amount of the crosslinking agent is about 0.01 to 5 parts by weight, and can be 0.05 parts by weight or more, 0.1 parts by weight or more, or 0.2 parts by weight or less, and can be 3 parts by weight or less, 2 parts by weight or less, or 1 part by weight or less, based on 100 parts by weight of the polymer.
[0193] (Other ingredients)
[0194] The PSA composition of the second embodiment may contain, in addition to the above-mentioned components, oligomers, tackifiers, silane coupling agents, chain transfer agents, plasticizers, softeners, anti-degradation agents, fillers, antioxidants, surfactants, antistatic agents, and the like.
[0195] In this embodiment, the first adhesive layer 1 and the second adhesive layer 2 can be adhesive layers formed by solvent-based adhesive compositions (third embodiment). The aforementioned solvent-based adhesive compositions at least contain a polymer and a solvent, and can contain a cross-linking agent. That is, the solvent-based adhesive composition used to form the adhesive layer of the third embodiment contains a polymer and a solvent, and can contain a cross-linking agent as needed.
[0196] [Third Method]
[0197] The pressure-sensitive adhesive layer of the third embodiment can be formed by applying a solvent-based pressure-sensitive adhesive composition containing a polymer and a solvent and, if necessary, a cross-linking agent onto a release film and then drying and removing the solvent.
[0198] <Solvent-based adhesive composition>
[0199] The solvent-based PSA composition for forming the PSA layer of the third embodiment contains a polymer and a solvent, and optionally contains a crosslinking agent.
[0200] (polymer)
[0201] As the polymer contained in the solvent-based pressure-sensitive adhesive composition, various polymers can be applied as in the first embodiment, and an acrylic polymer can be preferably used. The monomer components constituting the acrylic polymer are the same as in the first embodiment.
[0202] Third Embodiment In order to form a solid (fixed shape) PSA layer on a substrate, a polymer having a relatively large molecular weight can be used as the polymer contained in the solvent-based PSA composition. The weight average molecular weight of the polymer is, for example, about 100,000 to 2,000,000.
[0203] The aforementioned acrylic polymer contained in the solvent-based adhesive composition of the third embodiment may be a (meth)acrylic block copolymer. When the first adhesive layer 1 and / or the second adhesive layer 2 is formed of a solvent-based adhesive composition containing a (meth)acrylic block copolymer, since the height difference absorption is excellent and the processability is also excellent, the height difference of a plurality of LED chips arranged on the substrate of the display panel can be encapsulated without gaps without residual bubbles, and the processability is also excellent, so it is not easy to cause the adhesive layer to ooze out from the end during storage.
[0204] In this embodiment, the adhesive composition forming the first adhesive layer 1 is preferably a solvent-based adhesive composition containing a (meth) acrylic block copolymer. According to this scheme, the first adhesive layer 1 has excellent height difference absorption and excellent processability, and can encapsulate the height difference of multiple LED chips, metal wiring, etc. arranged on the substrate of the display panel without leaving any bubbles, thereby preventing color mixing between LED chips, improving the contrast of the image, and effectively preventing reflection caused by metal wiring, etc.
[0205] In this embodiment, it is preferred that the (meth)acrylic block copolymer has a high Tg segment having a glass transition temperature of 0°C to 100°C and a low Tg segment having a glass transition temperature of -100°C to below 0°C, and has tan δ peaks in the region above 0°C and in the region below 0°C.
[0206] In the present specification, a “high Tg segment having a glass transition temperature of 0° C. or higher and 100° C. or lower” is sometimes referred to as a “high Tg segment”, a “low Tg segment having a glass transition temperature of −100° C. or higher and lower than 0° C.” is sometimes referred to as a “low Tg segment”, a tan δ peak in the region of 0° C. or higher is sometimes referred to as a “high temperature region tan δ peak”, and a tan δ peak in the region lower than 0° C. is sometimes referred to as a “low temperature region tan δ peak”, a (meth)acrylic block copolymer having the high Tg segment, the low Tg segment, the high temperature region tan δ peak, and the low temperature region tan δ peak is sometimes referred to as a “(meth)acrylic block copolymer A”, and a solvent-based adhesive composition containing the (meth)acrylic block copolymer A is sometimes referred to as a “solvent-based adhesive composition A”.
[0207] The "segment" in the high Tg segment and the low Tg segment refers to a partial structure of each block unit constituting the (meth)acrylic block copolymer A.
[0208] The structure of the aforementioned (meth) acrylic block copolymer A may be a linear block copolymer, a branched (star-shaped) block copolymer, or a mixture thereof. The structure of such a block copolymer may be appropriately selected according to the physical properties of the desired block copolymer, and from the perspective of cost and ease of manufacture, a linear block copolymer is preferred. In addition, the linear block copolymer may be of any structure (arrangement), and from the perspective of the physical properties of the linear block copolymer or the physical properties of the solvent-based adhesive composition A, a block copolymer selected from (AB) is preferred. n Type, (AB) n-A type (n is an integer greater than 1, for example, an integer from 1 to 3) block copolymer of at least one structure. In these structures, A and B represent segments composed of different monomer compositions. In this specification, the segment represented by A constituting the aforementioned linear block copolymer is sometimes referred to as "A segment", and the segment represented by B is sometimes referred to as "B segment".
[0209] Among these, from the perspective of the physical properties of manufacturing ease, solvent-based adhesive composition A, it is preferably AB type diblock copolymer represented by AB, ABA type triblock copolymer represented by ABA, more preferably ABA type triblock copolymer. It can be considered that ABA type triblock copolymer is pseudo-crosslinked between the A segments at both ends, so that the cross-linked structure between the block copolymer becomes a more highly cross-linked structure, and the cohesion of the block copolymer is improved, and higher adhesion (adhesion) can be shown. It should be noted that in ABA type triblock copolymers, the 2 A segments at both ends can be the same as each other, or they can be different.
[0210] In the case where the (meth) acrylic block copolymer A is an ABA type triblock copolymer, at least one of the two A segments and one B segment (a total of 3) is a high Tg segment and at least another is a low Tg segment. From the perspective of the ease of manufacture, the physical properties of the solvent-based adhesive composition A, etc., it is preferred that the A segment is the aforementioned high Tg segment and the B segment is the aforementioned low Tg segment of the ABA type triblock copolymer. In this case, it is preferred that at least one of the two A segments is a high Tg segment and the B segment is an ABA type triblock copolymer of a low Tg segment, and more preferably the two A segments are both high Tg segments and the B segment is an ABA type triblock copolymer of a low Tg segment.
[0211] The glass transition temperature (Tg) of the high Tg segment constituting the (meth) acrylic block copolymer A is, as described above, 0°C or more and 100°C or less. By making the Tg of the high Tg segment in this range, there is a tendency that the storage modulus of the solvent-based adhesive composition A at room temperature (25°C) is easily controlled to be high, hard and excellent in processability, and the storage modulus is significantly reduced in the region exceeding 50°C, becoming a highly fluid adhesive composition. From the perspective of being able to improve the processability of the solvent-based adhesive composition A at room temperature (25°C), the Tg of the high Tg segment is preferably 4°C or more, more preferably 6°C or more, further preferably 8°C or more, further preferably 10°C or more, and particularly preferably 12°C or more. On the other hand, from the perspective that the storage modulus (G') of the solvent-based adhesive composition A is significantly reduced in the region exceeding 50°C and high fluidity is easily formed, the Tg of the high Tg segment is preferably 90°C or less, more preferably 85°C or less, further preferably 60°C or less, further preferably 50°C or less, and particularly preferably 35°C or less.
[0212] As described above, the Tg of the low Tg segment constituting the (meth) acrylic block copolymer A is -100°C or higher and lower than 0°C. By making the glass Tg of the low Tg segment in this range, there is a tendency that only the low Tg segment is fluidized at room temperature (25°C), and appropriate adhesion can be given to the solvent-based adhesive composition A while ensuring processability. From the perspective that the storage modulus of the solvent-based adhesive composition A is not easily reduced at room temperature (25°C) and processability can be improved, the Tg of the low Tg segment is preferably -95°C or higher, more preferably -90°C or higher, and further preferably -80°C or higher. On the other hand, from the perspective of being able to improve the appropriate adhesion and processability of the solvent-based adhesive composition A at room temperature (25°C), the Tg of the low Tg segment is preferably -5°C or lower, more preferably -10°C or lower, further preferably -20°C or lower, further preferably -30°C or lower, and particularly preferably -40°C or lower.
[0213] The difference in Tg between the high Tg segment and the low Tg segment constituting the (meth)acrylic block copolymer A (Tg of the high Tg segment - Tg of the low Tg segment) is not particularly limited, but is preferably 30°C or higher, more preferably 35°C or higher, more preferably 40°C or higher, more preferably 45°C or higher, further preferably 50°C or higher, particularly preferably 55°C or higher, preferably 120°C or lower, more preferably 115°C or lower, more preferably 110°C or lower, more preferably 105°C or lower, further preferably 100°C or lower, and particularly preferably 95°C or lower, from the viewpoint that the storage modulus of the solvent-based adhesive composition A at room temperature (25°C) is easily controlled to be high, hard and excellent in processability, and the storage modulus is significantly reduced in the region exceeding 50°C to obtain a highly fluid adhesive composition.
[0214] The glass transition temperature (Tg) of the high Tg segment and the low Tg segment constituting the (meth) acrylic block copolymer A is a calculated glass transition temperature calculated according to the following Fox equation. The calculated glass transition temperature is calculated based on the type and amount of each monomer component constituting the high Tg segment or the low Tg segment of the (meth) acrylic block copolymer A, and therefore can be adjusted by selecting the type and amount of the monomer component of each segment.
[0215] The glass transition temperature (Tg) can be calculated using the following Fox formula [1].
[0216] 1 / Calculate Tg = W1 / Tg(1)+W2 / Tg(2)+…+Wn / Tg(n)[1]
[0217] Here, W1, W2, ...Wn represent the weight fractions (weight %) of monomer component (1), monomer component (2), ...monomer component (n) constituting the copolymer relative to all monomer components, and Tg(1), Tg(2), ...Tg(n) represent the glass transition temperatures (in absolute temperature: K) of the homopolymers of monomer component (1), monomer component (2), ...monomer component (n).
[0218] It should be noted that the glass transition temperature of a homopolymer is known in various documents, product catalogs, etc., and is described, for example, in J. Brandup, EH Immergut, EA Grulke: Polymer Handbook: JOHN WILEY & SONS, INC. For monomers for which no numerical value is described in various documents, values measured by conventional thermal analysis, such as differential thermal analysis, dynamic viscoelasticity measurement, etc., can be used.
[0219] As mentioned above, the temperature region where the high temperature region tanδ peak of the (meth) acrylic block copolymer A appears is 0°C or more (for example, 0°C or more and 100°C or less). By making the high temperature region tanδ peak in this temperature range, there is a tendency that the storage modulus of the solvent-based adhesive composition A at room temperature (25°C) is easily controlled to be high, hard and excellent in processability, and the storage modulus is significantly reduced in the region exceeding 50°C, becoming a highly fluid adhesive composition. From the perspective of being able to improve the processability of the solvent-based adhesive composition A at room temperature (25°C), the temperature at which the high temperature region tanδ peak appears is preferably 3°C or more, more preferably 6°C or more, further preferably 9°C or more, further preferably 12°C or more, and particularly preferably 15°C or more. On the other hand, from the perspective that the storage modulus (G') of the solvent-based adhesive composition A is significantly reduced in the region exceeding 50°C and high fluidity is easily formed, the temperature at which the high temperature region tanδ peak appears is preferably 90°C or less, more preferably 80°C or less, further preferably 70°C or less, further preferably 65°C or less, and particularly preferably 60°C or less.
[0220] As described above, the temperature region where the low temperature region tanδ peak of the (meth) acrylic block copolymer A appears is lower than 0°C (e.g., -100°C or higher and lower than 0°C). By making the low temperature region tanδ peak in this temperature range, there is a tendency that only the low Tg segment is fluidized at room temperature (25°C), and appropriate adhesive force can be given to the solvent-based adhesive composition A while ensuring processability. From the perspective that the storage modulus of the solvent-based adhesive composition A is not easily reduced at room temperature (25°C) and processability can be improved, the temperature at which the low temperature region tanδ peak appears is preferably -95°C or higher, more preferably -90°C or higher, further preferably -80°C or higher, and further preferably -70°C or higher. On the other hand, from the perspective that the appropriate adhesive force and processability of the solvent-based adhesive composition A can be improved at room temperature (25°C), the temperature at which the low temperature region tanδ peak appears is preferably -5°C or lower, more preferably -10°C or lower, further preferably -20°C or lower, further preferably -30°C or lower, and particularly preferably -40°C or lower.
[0221] The maximum value of the tanδ peak in the high temperature region is not particularly limited, but is preferably 0.5 to 3.0. By making the maximum value of the tanδ peak in the high temperature region within this range, it is possible to achieve excellent processability and shape stability of the (meth) acrylic block copolymer A, which is preferred in this respect. From the perspective of achieving excellent processability, the maximum value of the tanδ peak in the high temperature region is preferably 0.6 or more, and more preferably 0.7 or more. In addition, from the perspective of not being prone to indentation, the maximum value of the tanδ peak in the high temperature region is preferably 2.5 or less, and more preferably 2.2 or less.
[0222] The maximum value of the tanδ peak in the low temperature region is not particularly limited, but is preferably 0.1 to 2.0. By making the maximum value of the tanδ peak in the low temperature region within this range, it is possible to achieve excellent processability and shape stability of the (meth) acrylic block copolymer A, which is preferred in this respect. From the perspective of achieving excellent processability, the maximum value of the tanδ peak in the high temperature region is preferably 0.2 or more, and more preferably 0.3 or more. In addition, from the perspective of not easily causing indentations, the maximum value of the tanδ peak in the low temperature region is preferably 1.5 or less, and more preferably 1 or less.
[0223] It should be noted that the high temperature region tan δ peak and the low temperature region tan δ peak, as well as the temperatures at which they appear and their maximum values, are measured by dynamic viscoelasticity measurement.
[0224] The (meth)acrylic block copolymer A is composed of a plurality of segments (including a high Tg segment and a low Tg segment) obtained by polymerizing a monomer component including a monomer (acrylic monomer) having a (meth)acryloyl group in the molecule.
[0225] The (meth)acrylic block copolymer A or each segment thereof preferably contains 70 wt % or more, more preferably 80 wt % or more, particularly preferably 90 wt % or more of the acrylic monomer based on the total amount of the monomer components (100 wt %).
[0226] The acrylic monomer constituting the (meth)acrylic block copolymer A or each segment thereof (including the high Tg segment and the low Tg segment) contains, as the main monomer units having the largest weight proportion, an alkyl acrylate having a linear or branched alkyl group and / or a monomer component derived from an alkyl methacrylate having a linear or branched alkyl group.
[0227] As the (meth)acrylic acid alkyl ester having a linear or branched alkyl group used to form the segment of the (meth)acrylic block copolymer A, specific examples of the (meth)acrylic acid alkyl ester having a chain alkyl group mentioned above can be cited. As the (meth)acrylic acid alkyl ester used for the aforementioned segment, one (meth)acrylic acid alkyl ester can be used, or two or more (meth)acrylic acid alkyl esters can be used. As the (meth)acrylic acid alkyl ester used for the aforementioned segment, at least one selected from the group consisting of methyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, tert-butyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, and isononyl acrylate is preferably used.
[0228] The segments of the (meth)acrylic block copolymer A may contain monomer units derived from alicyclic monomers. As alicyclic monomers used to form the monomer units of the aforementioned segments, specific examples of the aforementioned (meth)acrylic acid alkyl esters having alicyclic alkyl groups can be cited. The aforementioned alicyclic alkyl group may have a substituent. As the substituent, there can be cited: a halogen atom (e.g., a fluorine atom, a chlorine atom, a bromine atom, an iodine atom), a linear or branched alkyl group having 1 to 6 carbon atoms (e.g., a methyl group, an ethyl group, a n-propyl group, an isopropyl group, etc.). There is no particular limitation on the number of the aforementioned substituents, and they can be appropriately selected from 1 to 6. When there are two or more substituents, the two or more substituents may be the same or different. As the alicyclic monomers used for the aforementioned segments, one alicyclic monomer may be used, or two or more alicyclic monomers may be used. The alicyclic monomer used in the above-mentioned segment is preferably a cycloalkyl (meth)acrylate having a cycloalkyl group having 4 to 10 carbon atoms and optionally having a substituent (e.g., a linear or branched alkyl group having 1 to 6 carbon atoms), and more preferably at least one selected from the group consisting of cyclohexyl acrylate and 3,3,5-trimethylcyclohexyl (meth)acrylate.
[0229] The chain segments of the (meth)acrylic block copolymer A may contain monomer units derived from hydroxyl-containing monomers. Hydroxyl-containing monomers are monomers having at least one hydroxyl group in the monomer units. When the chain segments in the (meth)acrylic block copolymer A contain hydroxyl-containing monomer units, adhesion and appropriate cohesion are easily obtained in the solvent-based adhesive composition A.
[0230] As the hydroxyl-containing monomers used to form the monomer units of the aforementioned segments, specific examples of the above-mentioned hydroxyl-containing monomers can be cited. As the hydroxyl-containing monomers used for the aforementioned segments, one hydroxyl-containing monomer can be used, or two or more hydroxyl-containing monomers can be used. As the hydroxyl-containing monomers used for the aforementioned segments, hydroxyl-containing (meth)acrylates are preferred, and at least one selected from the group consisting of 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 4-hydroxybutyl acrylate, and 4-hydroxybutyl methacrylate is more preferred.
[0231] The chain segments of the (meth)acrylic block copolymer A may contain monomer units derived from nitrogen-containing monomers. Nitrogen-containing monomers are monomers having at least one nitrogen atom in the monomer unit. When the chain segments of the (meth)acrylic block copolymer A contain nitrogen-containing monomer units, hardness and good bonding reliability are easily obtained in the solvent-based adhesive composition A.
[0232] As the nitrogen-containing monomer used to form the aforementioned chain segment, the specific examples of the nitrogen-containing monomers mentioned above can be cited. As the nitrogen-containing monomer used for the acrylic polymer, one nitrogen-containing monomer can be used, or two or more nitrogen-containing monomers can be used. As the nitrogen-containing monomer used for the aforementioned chain segment, N-vinyl-2-pyrrolidone is preferably used.
[0233] The chain segments of the (meth)acrylic block copolymer A may contain monomer units derived from carboxyl-containing monomers. Carboxyl-containing monomers are monomers having at least one carboxyl group in the monomer unit. When the chain segments of the (meth)acrylic block copolymer A contain carboxyl-containing monomer units, good bonding reliability can sometimes be obtained in the solvent-based adhesive composition A.
[0234] As the carboxyl-containing monomers for forming the monomer units of the aforementioned segments, the specific examples of the above-mentioned carboxyl-containing monomers can be listed. As the carboxyl-containing monomers for the aforementioned segments, one carboxyl-containing monomer can be used, or two or more carboxyl-containing monomers can be used. As the carboxyl-containing monomers for the aforementioned segments, acrylic acid is preferably used.
[0235] Furthermore, as the monomer units for forming the aforementioned segments, the aforementioned other monomers can be cited. The content of the other monomers in the monomer units constituting the segments of the (meth)acrylic block copolymer A is not particularly limited as long as it is 30 wt % or less relative to the total amount of the monomer components (100 wt %), and can be appropriately selected within the range that does not impair the effects of the present invention.
[0236] As the monomer component constituting the high Tg segment of the (meth)acrylic block copolymer A, it is preferred that the monomer component contains a (meth)acrylic acid alkyl ester selected from a group consisting of a (meth)acrylic acid alkyl ester having a linear alkyl group having 1 to 3 carbon atoms (hereinafter sometimes referred to as “(meth)acrylic acid C 1-3 Straight-chain alkyl esters”), (meth)acrylic acid alkyl esters having a branched-chain alkyl group having 3 or 4 carbon atoms (hereinafter sometimes referred to as “(meth)acrylic acid C 3-4 At least one of the group consisting of a branched alkyl ester ("branched alkyl ester") and an alicyclic monomer. The homopolymers of these monomers have a relatively high Tg, so by containing a monomer selected from them as a monomer component constituting a high Tg segment, it is easy to control the Tg of the high Tg segment within the range specified in the present invention.
[0237] The alicyclic monomer is preferably a cycloalkyl (meth)acrylate having a cycloalkyl group having 4 to 10 carbon atoms and optionally having a substituent (e.g., a linear or branched alkyl group having 1 to 6 carbon atoms), more preferably a cycloalkyl (meth)acrylate having a cycloalkyl group having 4 to 10 carbon atoms and optionally having a substituent (e.g., a linear or branched alkyl group having 1 to 6 carbon atoms), and particularly preferably cyclohexyl acrylate (homopolymer Tg: 15° C.) and 3,3,5-trimethylcyclohexyl (meth)acrylate (homopolymer Tg: 52° C.).
[0238] When an alicyclic monomer is contained as a monomer component constituting the high Tg segment, the content of the alicyclic monomer relative to the total amount of the monomer components (100 wt %) is preferably 10 wt % or more (e.g., 10 to 100 wt %), more preferably 20 wt % or more, more preferably 30 wt % or more, more preferably 30 wt % or more, more preferably 40 wt % or more, more preferably 50 wt % or more, more preferably 60 wt % or more, more preferably 70 wt % or more, more preferably 80 wt % or more, more preferably 80 wt % or more, further preferably 90 wt % or more, particularly preferably 95 wt % or more, from the viewpoint of easily controlling the Tg of the high Tg segment within a predetermined range and providing the (meth)acrylic block copolymer A with desired properties.
[0239] As the aforementioned (meth)acrylic acid C 1-3 Straight chain alkyl ester, preferably acrylic acid C 1-3 The linear alkyl ester is particularly preferably methyl acrylate (Tg of the homopolymer: 8°C).
[0240] As the aforementioned (meth)acrylic acid C 3-4 Branched alkyl ester, preferably acrylic acid C 3-4 The branched alkyl ester is particularly preferably tert-butyl acrylate (Tg of the homopolymer: 35°C).
[0241] The monomer component constituting the high Tg segment contains (meth)acrylic acid C 1-3 Straight chain alkyl ester and / or (meth) acrylic acid C 3-4 In the case of branched alkyl esters, (meth)acrylic acid C 1-3 Straight chain alkyl ester and / or (meth) acrylic acid C 3-4The content of the branched alkyl ester relative to the total amount of the monomer components (100% by weight) is preferably 10% by weight or more (e.g., 10 to 100% by weight), more preferably 20% by weight or more, more preferably 30% by weight or more, more preferably 30% by weight or more, more preferably 40% by weight or more, more preferably 50% by weight or more, more preferably 60% by weight or more, more preferably 70% by weight or more, more preferably 80% by weight or more, more preferably 80% by weight or more, further preferably 90% by weight or more, particularly preferably 95% by weight or more, from the viewpoint of being able to easily control the Tg of the high Tg segment within a predetermined range and to impart desired physical properties to the (meth)acrylic block copolymer A.
[0242] As the monomer component constituting the low Tg segment of the (meth)acrylic block copolymer A, it is preferred that the monomer component contains a (meth)acrylic acid alkyl ester (hereinafter sometimes referred to as “(meth)acrylic acid C ester”) selected from the group consisting of a (meth)acrylic acid alkyl ester having a linear or branched alkyl group having 4 to 18 carbon atoms, from the viewpoint of being able to easily control the Tg of the low Tg segment within a predetermined range and imparting desired physical properties to the (meth)acrylic block copolymer A. 4-18 At least one of the group consisting of (meth)acrylic acid C 4-18 Homopolymers of alkyl esters have a relatively low Tg, so by including them as monomer components constituting the low Tg segments, it is easy to control the Tg of the low Tg segments within the range specified in the present invention. On the other hand, hydroxyl-containing monomers also have a relatively low Tg, and thus, it is easy to obtain adhesion and appropriate cohesion in the (meth)acrylic block copolymer A. Therefore, as a monomer component constituting the low Tg segments of the (meth)acrylic block copolymer A, it is further preferred to include (meth)acrylic acid C 4-18 Both alkyl esters and hydroxyl-containing monomers.
[0243] As the aforementioned (meth)acrylic acid C 4-18 Alkyl esters, preferably acrylic acid C 4-18 Alkyl esters, particularly preferred are butyl acrylate (homopolymer Tg: -55°C), 2-ethylhexyl acrylate (homopolymer Tg: -70°C), n-hexyl acrylate (homopolymer Tg: -57°C), n-octyl acrylate (homopolymer Tg: -65°C), and isononyl acrylate (homopolymer Tg: -58°C).
[0244] The monomer component constituting the low Tg segment contains (meth) acrylic acid C 4-18 In the case of alkyl esters, regarding (meth)acrylic acid C 4-18The content of the alkyl ester relative to the total amount of the monomer components (100% by weight) is preferably 10% by weight or more (e.g., 10 to 100% by weight), more preferably 20% by weight or more, more preferably 30% by weight or more, more preferably 30% by weight or more, more preferably 40% by weight or more, more preferably 50% by weight or more, more preferably 60% by weight or more, more preferably 70% by weight or more, more preferably 80% by weight or more, more preferably 80% by weight or more, further preferably 90% by weight or more, particularly preferably 95% by weight or more, from the viewpoint of easily controlling the Tg of the low Tg segment within a predetermined range and providing the (meth)acrylic block copolymer A with desired properties.
[0245] As the hydroxyl group-containing monomer, hydroxyl group-containing alkyl (meth)acrylate is preferred, and 4-hydroxybutyl acrylate (homopolymer Tg: -65°C) and 2-hydroxyethyl acrylate (homopolymer Tg: -15°C) are particularly preferred.
[0246] When a hydroxyl-containing monomer is contained as a monomer component constituting the low Tg segment, the content of the hydroxyl-containing monomer relative to the total amount of the monomer component (100% by weight) is preferably 1% by weight or more, more preferably 1.5% by weight or more, more preferably 2% by weight or more, further preferably 2.5% by weight or more, and particularly preferably 3% by weight or more, from the viewpoint of being able to easily control the Tg of the low Tg segment within a predetermined range and being able to impart desired physical properties to the (meth)acrylic block copolymer A. On the other hand, the content of the hydroxyl-containing monomer relative to the total amount of the monomer component (100% by weight) is preferably 50% by weight or less, more preferably 40% by weight or less, more preferably 30% by weight or less, more preferably 20% by weight or less, further preferably 10% by weight or less, and particularly preferably 5% by weight or less.
[0247] The monomer component constituting the low Tg segment of the (meth)acrylic block copolymer A contains (meth)acrylic acid C 4-18 In the case of both alkyl ester and hydroxyl-containing monomer, the hydroxyl-containing monomer and (meth) acrylic acid C 4-18 Alkyl ester ratio (hydroxyl-containing monomer / (meth)acrylic acid C 4-18 The lower limit is preferably 1 / 99, more preferably 1.5 / 98.5, more preferably 2 / 98, further preferably 2.5 / 97.5, and particularly preferably 3 / 97. On the other hand, the upper limit is preferably 50 / 50, more preferably 40 / 60, more preferably 30 / 70, and further preferably 20 / 80.
[0248] The (meth)acrylic block copolymer A can be produced by the living radical polymerization of the above-mentioned monomer components. The living radical polymerization method is preferred in the following aspects: while maintaining the simplicity and versatility of the existing free radical polymerization method, it is not easy to cause termination reaction and chain transfer, and the growth end will not be deactivated and grow, so it is easy to precisely control the molecular weight distribution and produce a polymer with uniform composition.
[0249] In the living radical polymerization method, a high Tg segment can be prepared first and then the monomer of the low Tg segment can be polymerized with the high Tg segment; or a low Tg segment can be prepared first and then the monomer of the high Tg segment can be polymerized with the low Tg segment.
[0250] When the (meth)acrylic block copolymer A is an ABA type triblock copolymer, it is preferred to first produce the A segment and then polymerize the monomer of the B segment with the A segment from the viewpoint of ease of production.
[0251] The living radical polymerization method can be any known method without particular limitation. Depending on the method for stabilizing the polymerization growth end, there are methods such as: a method using a transition metal catalyst (ATRP method); a method using a sulfur-based reversible addition-fragmentation chain transfer agent (RAFT agent) (RAFT method); a method using an organic tellurium compound (TERP method). Among these methods, the RAFT method is preferably used from the perspectives of the diversity of monomers that can be used, the ease of molecular weight control, and the fact that no metal remains in the solvent-based adhesive composition.
[0252] The RAFT method can use a known method without particular limitation, and for example, comprises the following steps: step 1, for example, using a RAFT agent to polymerize a monomer component to prepare a first segment (first RAFT polymerization); and step 2, further adding / polymerizing a monomer component having a different monomer composition from that in step 1 to the first segment obtained in step 1, to add a second segment to the first segment (second RAFT polymerization). After the second RAFT polymerization, the third, fourth, ... RAFT polymerizations are further performed in the same manner as the second RAFT polymerization, and the third, fourth, ... segments can be further added.
[0253] The above-mentioned steps 1 and 2 can be carried out by known and commonly used methods, for example, solution polymerization method, emulsion polymerization method, bulk polymerization method, polymerization method based on heat and active energy ray irradiation (thermal polymerization method, active energy ray polymerization method), etc. Among them, solution polymerization method is preferred in terms of transparency, water resistance, cost, etc. It should be noted that the polymerization is preferably carried out by avoiding contact with oxygen from the perspective of suppressing polymerization inhibition caused by oxygen. For example, it is preferred to carry out the polymerization under a nitrogen atmosphere.
[0254] When the (meth)acrylic block copolymer A is an ABA type triblock copolymer, it is preferably prepared by preparing the A segment in the above step 1 and adding the B segment to the obtained A segment in the above step 2. In this case, the A segment is preferably a high Tg segment and the B segment is preferably a low Tg segment.
[0255] As the RAFT agent, a known substance can be used without particular limitation, and for example, a compound represented by the following formula (1), formula (2), or formula (3) (trithiocarbonate, dithioester, dithiocarbonate) is preferred.
[0256]
[0257] In formula (1), formula (2), or formula (3) [formula (1) to (3)], R 1a and R 1b are the same or different and represent a hydrogen atom, a hydrocarbon group or a cyano group. 1c represents a hydrocarbon group which may have a cyano group. 1a , R 1b and R 1c Examples of the hydrocarbon group include hydrocarbon groups having 1 to 20 carbon atoms (straight-chain, branched or cyclic saturated or unsaturated hydrocarbon groups, etc.), and hydrocarbon groups having 1 to 12 carbon atoms are preferred. Specific examples of the hydrocarbon group include: methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, cyclohexyl, dodecyl, octadecyl and other straight-chain, branched or cyclic alkyl groups having 1 to 12 carbon atoms; phenyl and other aryl groups having 6 to 12 carbon atoms; benzyl, phenethyl and other arylalkyl groups having a total of 7 to 10 carbon atoms. 1c Examples of the hydrocarbon group having a cyano group include groups in which 1 to 3 hydrogen atoms possessed by the above hydrocarbon groups are substituted with cyano groups.
[0258] In formulas (1) to (3), R 2 It represents a hydrocarbon group or a group in which a part of hydrogen atoms possessed by the hydrocarbon group is replaced by a carboxyl group (for example, a carboxylalkyl group). Examples of the above hydrocarbon group include hydrocarbon groups having 1 to 20 carbon atoms (straight-chain, branched or cyclic saturated or unsaturated hydrocarbon groups, etc.), among which hydrocarbon groups having 1 to 12 carbon atoms are preferred. Specifically, examples of the hydrocarbon group include: methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, cyclohexyl, dodecyl, octadecyl and other straight-chain, branched or cyclic alkyl groups having 1 to 12 carbon atoms; benzyl, phenethyl and other arylalkyl groups having a total carbon number of 7 to 10.
[0259] In the RAFT method, polymerization is carried out by reacting the raw material monomer so as to be inserted between the sulfur atom in the RAFT agent represented by formulas (1) to (3) and the methylene group adjacent to the sulfur atom.
[0260] Most of the above-mentioned RAFT agents are commercially available. Those that are not commercially available can be easily synthesized using known conventional methods. It should be noted that in the present invention, the RAFT agent may be used alone or in combination of two or more.
[0261] Examples of the RAFT agent include trithiocarbonates such as dibenzyl trithiocarbonate and S-cyanomethyl-S-dodecyl trithiocarbonate; dithioesters such as cyanoethyl dithiopropionate, benzyl dithiopropionate, benzyl dithiobenzoate, and acetoxyethyl dithiobenzoate; and dithiocarbonates such as O-ethyl-S-(1-phenylethyl) dithiocarbonate, O-ethyl-S-(2-propoxyethyl) dithiocarbonate, and O-ethyl-S-(1-cyano-1-methylethyl) dithiocarbonate. Among them, trithiocarbonates are preferred, and trithiocarbonates having a bilaterally symmetrical structure in formula (1) are more preferred, and dibenzyl trithiocarbonate and bis{4-[ethyl-(2-acetoxyethyl)carbamoyl]benzyl} trithiocarbonate are particularly preferred.
[0262] The above-mentioned step 1 can be carried out by polymerizing the monomer components in the presence of a RAFT agent. The amount of the RAFT agent used in step 1 is usually 0.05 to 20 parts by weight, preferably 0.05 to 10 parts by weight, relative to 100 parts by weight of the total amount of the monomer components. If such an amount is used, it is easy to control the reaction and also easy to control the weight average molecular weight of the obtained segment.
[0263] The step 2 can be performed by adding monomer components to the polymerization reaction mixture obtained in the step 1 and performing further polymerization.
[0264] The RAFT method is preferably carried out in the presence of a polymerization initiator. As the polymerization initiator, for example, a common organic polymerization initiator can be listed, and specifically, a peroxide and an azo compound can be listed, among which azo compounds are preferred. The polymerization initiator can be used alone or in combination of two or more.
[0265] As a peroxide type polymerization initiator, benzoyl peroxide and t-butyl permaleate are mentioned, for example.
[0266] Examples of the azo compound include 2,2'-azobisisobutyronitrile, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2-cyclopropylpropionitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2-(carbamoylazo)isobutyronitrile, 2-phenylazo-4-methoxy-2,4 -Dimethylvaleronitrile, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis(N,N'-dimethyleneisobutylamidine), 2,2'-azobis(isobutylamide) dihydrate, 4,4'-azobis(4-cyanopentanoic acid), 2,2'-azobis(2-cyanopropanol), dimethyl-2,2'-azobis(2-methylpropionate), 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide].
[0267] The amount of the polymerization initiator used is usually 0.001 to 2 parts by weight, preferably 0.002 to 1 part by weight, based on 100 parts by weight of the total amount of the monomer components. If used in such an amount, the weight average molecular weight of the obtained segment can be easily controlled.
[0268] The RAFT method can be a bulk polymerization without using a polymerization solvent, but it is preferred to use a polymerization solvent. Examples of polymerization solvents include aromatic hydrocarbons such as benzene, toluene, and xylene; aliphatic hydrocarbons such as n-pentane, n-hexane, n-heptane, and n-octane; alicyclic hydrocarbons such as cyclopentane, cyclohexane, cycloheptane, and cyclooctane; halogenated hydrocarbons such as chloroform, carbon tetrachloride, 1,2-dichloroethane, and chlorobenzene; ethers such as diethyl ether, diisopropyl ether, 1,2-dimethoxyethane, dibutyl ether, tetrahydrofuran, dioxane, anisole, phenethyl ether, and diphenyl ether; esters such as ethyl acetate, propyl acetate, butyl acetate, and methyl propionate; ketones such as acetone, methyl ethyl ketone, diethyl ketone, methyl isobutyl ketone, and cyclohexanone; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; nitriles such as acetonitrile and benzonitrile; sulfoxides such as dimethyl sulfoxide and cyclopentane. The polymerization solvent may be used alone or in combination of two or more.
[0269] The amount of the polymerization solvent used is not particularly limited, but is preferably 0.01 mL or more, more preferably 0.05 mL or more, further preferably 0.1 mL or more, and preferably 50 mL or less, more preferably 10 mL or less, further preferably 1 mL or less, for example, relative to 1 g of the monomer component.
[0270] The reaction temperature under the RAFT method is usually 60 to 120° C., preferably 70 to 110° C., and is usually carried out under an inert gas atmosphere such as nitrogen. The reaction can be carried out under any conditions of normal pressure, pressurization and reduced pressure, and is usually carried out under normal pressure. In addition, the reaction time is usually 1 to 20 hours, preferably 2 to 14 hours.
[0271] The polymerization reaction conditions of the RAFT method described above can be applied to step 1 and step 2, respectively.
[0272] After the polymerization reaction is completed, the target (meth)acrylic block copolymer A can be isolated by removing the used solvent and residual monomers from the obtained reaction mixture by conventional separation and purification means.
[0273] When the high Tg segment or low Tg segment of the (meth)acrylic block copolymer A is prepared in the above step 1, the weight average molecular weight (Mw) of the high Tg segment or low Tg segment is not particularly limited, but is preferably 10,000 to 1,000,000, more preferably 50,000 to 500,000, and further preferably 100,000 to 300,000. The Mw of the high Tg segment or low Tg segment within this range is suitable for the above-mentioned effect of the present invention.
[0274] When two or more high Tg segments or low Tg segments exist in the (meth)acrylic block copolymer A, the above-mentioned Mw is the sum of the Mw thereof.
[0275] The weight average molecular weight (Mw) of the (meth)acrylic block copolymer A is not particularly limited, but is preferably 200,000 or more, more preferably 300,000 to 5,000,000, and even more preferably 400,000 to 2,500,000. The Mw of the (meth)acrylic block copolymer A within this range is suitable for the effects of the present invention.
[0276] The molecular weight distribution (Mw / Mn) of the (meth)acrylic block copolymer A is not particularly limited, but is preferably greater than 1, more preferably 1.5 or more, further preferably 2 or more, particularly preferably 2.5 or more, and preferably 5 or less, more preferably 4.5 or less, further preferably 4 or less, and particularly preferably 3.5 or less.
[0277] It should be noted that the weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) are measured by the GPC method.
[0278] The content of the high Tg segment in the (meth)acrylic block copolymer A is preferably 10 wt% or more, more preferably 20 wt% or more, further preferably 25 wt% or more, particularly preferably 30 wt% or more, and is preferably 95 wt% or less, more preferably 90 wt% or less, further preferably 85 wt% or less, based on 100 wt% of the entire (meth)acrylic block copolymer A.
[0279] The content of the low Tg segment in the (meth)acrylic block copolymer A is preferably 5 wt% or more, more preferably 10 wt% or more, further preferably 15 wt% or more, and is preferably 60 wt% or less, more preferably 50 wt% or less, further preferably 40 wt% or less, and particularly preferably 30 wt% or less, based on 100 wt% of the entire (meth)acrylic block copolymer A.
[0280] The content of each segment and their ratio can be calculated based on the weight average molecular weight (Mw) of each segment or (meth)acrylic block copolymer A obtained in each step of the RAFT method, and can be controlled by the addition ratio of monomers when forming each segment and the polymerization rate of each monomer.
[0281] The content of the (meth)acrylic block copolymer A in the solvent-based adhesive composition A is not particularly limited, but is preferably 50% by weight or more (e.g., 50 to 100% by weight), more preferably 60% by weight or more, further preferably 80% by weight or more, and particularly preferably 90% by weight or more, relative to the total amount of the solvent-based adhesive composition A (total weight, 100% by weight), from the viewpoint of obtaining excellent processability at room temperature (25°C) and excellent height difference absorption in a region exceeding 50°C.
[0282] (Solvent)
[0283] Since the polymer in the third embodiment is solid, the solvent-based adhesive composition is a solution of the polymer dissolved in an organic solvent. For example, a polymer solution can be obtained by solution polymerization of the monomer components. A solid polymer can be dissolved in an organic solvent to prepare a polymer solution.
[0284] As the solvent, ethyl acetate, toluene, etc. are generally used. The concentration of the solution is usually about 20 to 80% by weight.
[0285] As a polymerization initiator for solution polymerization of monomer components, thermal polymerization initiators such as azo initiators, peroxide initiators, and redox initiators obtained by combining peroxides and reducing agents (for example, combinations of persulfates and sodium bisulfite, combinations of peroxides and sodium ascorbate) are preferably used. There is no particular limitation on the amount of the polymerization initiator used. For example, with respect to 100 parts by weight of the total monomer components forming the polymer, it is preferably about 0.005 to 5 parts by weight, more preferably about 0.02 to 3 parts by weight.
[0286] (Colorant)
[0287] The solvent-based adhesive composition for forming the adhesive layer of the third mode may contain a colorant. In particular, the solvent-based adhesive composition for forming the first adhesive layer 1 preferably further contains a colorant. If the solvent-based adhesive composition for forming the first adhesive layer 1 contains a colorant, it is preferable in the following aspects: the light transmittance of the first adhesive layer 1 to visible light is reduced, and a scheme in which the aforementioned T1 and the aforementioned T2 satisfy T1 < T2 is formed. By encapsulating the metal wiring layer 6 and the LED chip of the self-luminous display device (Mini / Micro LED display device) of the present embodiment with the first adhesive layer 1 having reduced light transmittance to visible light and being given light-shielding properties, reflection caused by metal wiring and the like can be prevented, color mixing between LED chips can be prevented, and the contrast of the image can be improved.
[0288] The colorant may be a dye or a pigment as long as it can be dissolved or dispersed in the solvent-based adhesive composition. From the perspective that low haze can be achieved with a small amount of addition and it is easy to be uniformly distributed without sedimentation like a pigment, a dye is preferred. In addition, from the perspective of obtaining high color development with a small amount of addition, a pigment is also preferred. When a pigment is used as the colorant, a pigment with low conductivity or no conductivity is preferred. In addition, when a dye is used, it is preferably used in combination with an antioxidant and the like described later.
[0289] As the colorant contained in the solvent-based adhesive composition in the third mode, in addition to the ultraviolet light-transmitting colorant described above for the first mode, an ultraviolet light-absorbing colorant is also included.
[0290] Examples of the ultraviolet light-transmitting black pigment include "9050BLACK", "UVBK-0001", etc. manufactured by TOKUSHIKI CO., Ltd. Examples of the ultraviolet light-absorbing black dye include "VALIFAST BLACK 3810", "NUBIAN Black PA-2802", etc. manufactured by ORIENT CHEMICAL INDUSTRIES CO., LTD. Examples of the ultraviolet light-absorbing black pigment include carbon black, titanium black, etc.
[0291] The content of the colorant in the solvent-based adhesive composition is, for example, about 0.01 to 20 parts by weight relative to 100 parts by weight of the total monomer amount, and can be appropriately set according to the type of the colorant, the color tone of the adhesive layer, the light transmittance, etc. The colorant can be added to the composition as a solution or dispersion dissolved or dispersed in an appropriate solvent.
[0292] (Crosslinking agent)
[0293] The solvent-based PSA composition of the third embodiment may contain a crosslinking agent capable of crosslinking with the above polymer. When the solvent-based PSA composition contains a (meth)acrylic block copolymer, the PSA layer of the third embodiment may not contain a crosslinking agent because it has sufficient shape stability.
[0294] In the third aspect, when the solvent-based PSA composition contains a crosslinking agent, the crosslinking agent is preferably an isocyanate crosslinking agent or an epoxy crosslinking agent, as described above with respect to the second aspect.
[0295] In the third embodiment, when the solvent-based adhesive composition contains a cross-linking agent, its content is about 0.01 to 5 parts by weight relative to 100 parts by weight of the polymer, and can be more than 0.05 parts by weight, more than 0.1 parts by weight, or more than 0.2 parts by weight, and can be less than 3 parts by weight, less than 2 parts by weight, or less than 1 part by weight.
[0296] (Other ingredients)
[0297] The solvent-based PSA composition of the third embodiment may contain, in addition to the above-mentioned components, oligomers, tackifiers, silane coupling agents, chain transfer agents, plasticizers, softeners, anti-degradation agents, fillers, antioxidants, surfactants, antistatic agents, and the like.
[0298] <Optical laminate>
[0299] In this embodiment, the optical laminate 10 can be prepared by laminating the first adhesive layer 1 and the second adhesive layer 2 on both surfaces of the first substrate S. The order of laminating the first adhesive layer 1 and the second adhesive layer 2 on both surfaces of the first substrate S is not particularly limited.
[0300] In the present embodiment, the optical layered bodies 20 to 22 can be prepared by laminating the second pressure-sensitive adhesive layer 2 of the optical layered body 10 on one surface of the second substrate 3 (the surface not subjected to the antireflection treatment and / or antiglare treatment when the treatment is performed).
[0301] The optical laminates 20 to 22 can also be prepared by laminating the second adhesive layer 2, the first substrate S, and the first adhesive layer 1 in this order on one side of the second substrate 3 (the side not subjected to the anti-reflection treatment and / or anti-glare treatment when the treatment is performed).
[0302] [First method]
[0303] There is no particular limitation on the method of laminating the first adhesive layer 1 and the second adhesive layer 2 of the first mode on the first substrate S. For example, the photocurable adhesive composition can be coated on a release film and formed into a sheet, and then photocured to produce the sheet-like first adhesive layer 1 and the second adhesive layer 2, and then they can be respectively laminated on both sides of the first substrate S.
[0304] The method of laminating the second adhesive layer 2 of the optical laminate 10 on a single side of the second substrate 3 (the side that has not been treated with anti-reflection and / or anti-glare treatment when the treatment has been performed), and the method of laminating them in the order of the second adhesive layer 2, the first substrate S and the first adhesive layer 1 on a single side of the second substrate 3 (the side that has not been treated with anti-reflection and / or anti-glare treatment when the treatment has been performed) can also be performed by the same bonding.
[0305] The first adhesive layer or the second adhesive layer of the first mode can be obtained by coating a photocurable adhesive composition on a release film in a sheet (layer), irradiating the coating film of the adhesive composition on the release film with ultraviolet rays, and photocuring. When photocuring, it is preferred to further attach a release film to the surface of the coating film, and irradiate the photocurable adhesive composition with ultraviolet rays in a state of being sandwiched between two release films to prevent polymerization inhibition caused by oxygen. Before photocuring, the sheet-like coating film can be heated for the purpose of removing the solvent or dispersion medium of the colorant. In the case of removing the solvent by heating, it is preferably implemented before attaching the release film.
[0306] As a film substrate for a peeling film, a film formed of various resin materials can be used. As resin materials, polyester resins such as polyethylene terephthalate and polyethylene naphthalate, acetate resins, polyethersulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth) acrylic resins, polyvinyl chloride resins, polyvinylidene chloride resins, polystyrene resins, polyvinyl alcohol resins, polyarylate resins, polyphenylene sulfide resins, etc. can be listed. Among these, polyester resins such as polyethylene terephthalate are particularly preferred. The thickness of the film substrate is preferably 10 to 200 μm, more preferably 25 to 150 μm. As materials for the release layer, silicone release agents, fluorine release agents, long-chain alkyl release agents, fatty acid amide release agents, etc. can be listed. The thickness of the release layer is generally about 10 to 2000 nm.
[0307] As a method for coating the adhesive composition on the release film, various methods such as roll coating, lick roll coating, gravure coating, reverse coating, roll brush, spray coating, dip roll coating, rod coating, knife coating, air knife coating, curtain coating, lip coating, and die coater can be used.
[0308] The thickness of the first adhesive layer 1 is not particularly limited, and can be appropriately set in such a manner that the upper part (image display side) of the light-emitting element is covered by the first substrate S and the second adhesive layer 2 while the light-emitting element arranged on the display panel described later is fully encapsulated. For example, the thickness of the first adhesive layer is adjusted to be 1.0 to 4.0 times, preferably 1.1 to 3.0 times, more preferably 1.2 to 2.5 times, and further preferably 1.3 to 2.0 times the height of the light-emitting element. Specifically, the thickness of the first adhesive layer is, for example, about 10 to 300 μm, preferably 15 to 200 μm. Specifically, the thickness of the first adhesive layer can be more than 10 μm, more than 15 μm, more than 20 μm, more than 30 μm, more than 40 μm, or more than 50 μm. In addition, in the case where the first adhesive layer contains a colorant that is transparent to ultraviolet light, even if the thickness of the first adhesive layer is large, the photocurable adhesive composition can be uniformly photocured in the thickness direction. The thickness of the first adhesive layer is 300 μm or less, and may be 250 μm or less, or 200 μm or less.
[0309] The thickness of the second adhesive layer 2 is not particularly limited, and can be appropriately set in a manner that allows light to fully pass through the upper part of the light-emitting element (image display side). Specifically, the thickness of the second adhesive layer is, for example, about 1 to 500 μm, more preferably 10 to 300 μm, and further preferably 15 to 200 μm. Specifically, the thickness of the second adhesive layer can be more than 1 μm, more than 10 μm, more than 15 μm, more than 20 μm, more than 30 μm, more than 40 μm, or more than 50 μm. In addition, the thickness of the second adhesive layer can be less than 400 μm, less than 300 μm, less than 250 μm, or less than 200 μm.
[0310] The ratio of the thickness of the second adhesive layer to the thickness of the first adhesive layer (the thickness of the second adhesive layer / the thickness of the first adhesive layer) is not particularly limited, and can be appropriately set in such a manner that the light-emitting elements arranged on the display panel described later are fully encapsulated while the upper part (image display side) of the light-emitting elements is covered by the second adhesive layer. Specifically, (the thickness of the second adhesive layer / the thickness of the first adhesive layer) can be, for example, about 1.0 to 5.0, preferably 1.2 to 4.0, and more preferably 1.3 to 3.0.
[0311] By irradiating the photocurable adhesive composition coated in a layer on the release film with ultraviolet rays, active species are generated from the photopolymerization initiator, the photopolymerizable compound is polymerized, and the liquid photocurable adhesive composition forms a solid (fixed shape) adhesive layer with an increase in the polymerization rate (reduction in unreacted monomers). The light source for ultraviolet irradiation is not particularly limited as long as it can irradiate light in the wavelength range to which the photopolymerization initiator contained in the photocurable adhesive composition has sensitivity, and LED light sources, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, xenon lamps, etc. can be used.
[0312] The cumulative amount of irradiation light is, for example, 100 to 5000 mJ / cm 2 The polymerization rate (non-volatile component) of the adhesive layer formed by the photocured product of the photocurable adhesive composition is preferably 80% or more, more preferably 85% or more, and further preferably 90% or more. The polymerization rate may be 93% or more or 95% or more. In order to reduce the non-volatile component, the adhesive layer may be heated to remove volatile components such as residual monomers, unreacted polymerization initiators, and solvents.
[0313] In the case where release films are provided on both sides of the adhesive layer, the thickness of the release film on one side may be the same as or different from the thickness of the release film on the other side. The release force when the release film temporarily bonded to one side is peeled off from the adhesive layer may be the same as or different from the release force when the release film temporarily bonded to the other side is peeled off from the adhesive layer. In the case where the release forces of the two are different, the optical laminate 10 having the first adhesive layer and the second adhesive layer in the first mode can be prepared by firstly peeling off the release film (light release film) with relatively small release force from the first adhesive layer 1 and the second adhesive layer 2 respectively and laminating the first adhesive layer 1 and the second adhesive layer 2 on the two sides of the first substrate S respectively.
[0314] In addition, by coating the aforementioned photocurable adhesive composition on both sides of the first substrate S, respectively, forming it into a sheet, attaching a release film to the surface of the coating film, and irradiating ultraviolet rays, thereby laminating the first adhesive layer and the second adhesive layer on the first substrate S, respectively, the same as above is performed, and an optical laminate 10 having a first adhesive layer and a second adhesive layer of the first mode can also be produced.
[0315] When the first adhesive layer and / or the second adhesive layer contain a colorant, the colorant has light absorption for visible light. The visible light transmittance of the optical laminate of the first embodiment is, for example, 80% or less, and can be 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, or 5% or less.
[0316] In the first embodiment, the visible light transmittance T1 of the first adhesive layer is not particularly limited, and is, for example, 80% or less, and may be 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less. By making the visible light transmittance T1 of the first adhesive layer 80% or less, it is easy to make the transmittance lower than the visible light transmittance T2 of the second adhesive layer. As described above, by encapsulating the metal wiring and the light-emitting element of the self-luminous display device, it is possible to prevent reflection of the metal wiring, etc., prevent color mixing between the light-emitting elements, and improve contrast. In addition, as described above, when a colorant whose ultraviolet absorption is less than that of visible light is used in the first adhesive layer, the average transmittance T1 of the first adhesive layer at wavelengths of 330 to 400 nm is UV It will be greater than the average transmittance T of the wavelength 400~700nm VIS The average transmittance T of the first adhesive layer at a wavelength of 400 to 700 nm VIS For example, it is 80% or less, and may be 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less. The average transmittance T of the first adhesive layer at a wavelength of 330 to 400 nm UVIt is preferably 5% or more, and may be 10% or more, 15% or more, 20% or more, or 25% or more. UV With T VIS Difference T UV -T VIS It may be 3% or more, 5% or more, 8% or more, or 10% or more.
[0317] In the first embodiment, the visible light transmittance T2 of the second adhesive layer is not particularly limited, and is, for example, 85 to 100%, and may be 88% or more, 90% or more, or 92% or more. As described above, by covering the upper portion (image display side) of the light-emitting element of the self-luminous display device with the second adhesive layer having high transmittance, the light-emitting efficiency is improved.
[0318] In the first embodiment, the shear storage modulus G'25°C of the first adhesive layer and the second adhesive layer at a temperature of 25°C is, for example, about 10 to 1000 kPa, and can be 30 kPa or more, 50 kPa or more, 70 kPa or more, or 100 kPa or more, or 700 kPa or less, 500 kPa or less, 300 kPa or less, or 200 kPa or less. The shear storage modulus G'85°C of the adhesive layer at a temperature of 85°C is, for example, about 3 to 300 kPa, and can be 5 kPa or more, 7 kPa or more, or 10 kPa or more, or 200 kPa or less, 150 kPa or less, or 100 kPa or less. If the shear storage modulus of the adhesive layer is within the above range, it is possible to achieve both moderate softness and adhesion. The shear storage modulus is a measured value based on a dynamic viscoelasticity measurement at a frequency of 1 Hz.
[0319] [Second method]
[0320] The optical laminate 10 having the second-mode adhesive layer can be prepared as follows: the second-mode photocurable adhesive composition is applied onto a release film, the solvent is dried and removed as needed to form the first adhesive layer 1 and the second adhesive layer 2, and they are attached to both surfaces of the first substrate S, respectively.
[0321] Alternatively, the optical laminate 10 having the second embodiment of the pressure-sensitive adhesive layer can be prepared by applying the second embodiment of the photocurable pressure-sensitive adhesive composition to both surfaces of the first substrate 3 and, if necessary, drying and removing the solvent.
[0322] The optical laminates 20 to 22 having the second embodiment of the pressure-sensitive adhesive layer can be prepared by bonding the second pressure-sensitive adhesive layer 2 of the optical laminate 10 to one surface of the second substrate 3 (the surface not subjected to the antireflection treatment and / or antiglare treatment when the surface has been subjected to the antireflection treatment and / or antiglare treatment).
[0323] In addition, the optical laminate 20 to 22 having a second-mode adhesive layer can also be prepared by laminating the second adhesive layer 2, the first substrate S and the first adhesive layer 1 in this order on a single side of the second substrate 3 (the side that has not been subjected to anti-reflection treatment and / or anti-glare treatment when such treatment has been performed).
[0324] When the photocurable adhesive composition contains a solvent, the solvent is dried after the adhesive composition is applied. As a drying method, an appropriate method can be appropriately adopted according to the purpose. The heating drying temperature is preferably 40°C to 200°C, more preferably 50°C to 180°C, and particularly preferably 70°C to 170°C. The drying time can be appropriately adopted. The drying time is preferably 5 seconds to 20 minutes, more preferably 5 seconds to 15 minutes, and particularly preferably 10 seconds to 10 minutes.
[0325] After applying the photocurable adhesive composition, it can be heated as needed to introduce a crosslinked structure into the polymer. The heating temperature and heating time can be appropriately set according to the type of crosslinking agent used, usually in the range of 20°C to 160°C and about 1 minute to 7 days. The heating used to dry the solvent can also serve as the heating for crosslinking. The introduction of the crosslinked structure does not necessarily require heating.
[0326] The first adhesive layer and the second adhesive layer of the second embodiment preferably have the same thickness (each thickness of the first adhesive layer and the second adhesive layer, the ratio of the thickness), light transmittance, and shear storage modulus as the first adhesive layer and the second adhesive layer of the first embodiment. Since the first adhesive layer and the second adhesive layer of the second embodiment are not photocured, the photopolymerizable compound is contained in an unreacted state. That is, the first adhesive layer and the second adhesive layer of the second embodiment are photocurable adhesive layers containing a polymer, a photopolymerizable compound, a photopolymerization initiator, and a colorant as needed.
[0327] The optical laminate having the photocurable first adhesive layer and / or the second adhesive layer of the second mode can be photocured by irradiating ultraviolet rays after being attached to the display panel described later. The optical laminate can change the bonding force between the optical laminate and the display panel by photocuring. For example, the adhesive layer before photocuring has high flexibility, so it can fill the concave-convex shape and height difference formed by the light-emitting elements arranged on the display panel, and the bonding force and bonding reliability to the display panel can be improved after photocuring.
[0328] As the active ray for photocuring the adhesive layer, ultraviolet rays can be used. As in the first embodiment of the adhesive layer, when a colorant having ultraviolet light transmittance is used, since the transmittance of ultraviolet light is greater than that of visible light, even when the thickness of the adhesive layer is large, curing inhibition during photocuring can be suppressed.
[0329] The optical laminate having the first and second adhesive layers containing the ultraviolet-transmitting colorant absorbs visible light. The optical laminate of the first and second embodiments preferably has a maximum transmittance at 350 nm to 450 nm.
[0330] The visible light transmittance of the optical layered body of the first embodiment and the second embodiment is, for example, 80% or less, and may be 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, or 5% or less.
[0331] [Third Method]
[0332] The optical laminate 10 having the third-form adhesive layer can be prepared as follows: the solvent-based adhesive composition of the third form is applied onto a release film, the solvent is dried and removed as needed to form the first adhesive layer 1 and the second adhesive layer, which are respectively attached to both surfaces of the first substrate S.
[0333] The optical laminate 10 having the third embodiment of the adhesive layer can also be prepared by applying the solvent-based adhesive composition of the third embodiment on both surfaces of the first substrate S and, if necessary, drying and removing the solvent to form the first adhesive layer 1 and the second adhesive layer.
[0334] The optical laminates 20 to 22 having the third embodiment of the pressure-sensitive adhesive layer can be prepared by bonding the second pressure-sensitive adhesive layer 2 of the optical laminate 10 to one surface of the second substrate 3 (the surface not subjected to the antireflection treatment and / or antiglare treatment when the surface has been subjected to the antireflection treatment and / or antiglare treatment).
[0335] In addition, the optical laminate 20 to 22 having a third-party adhesive layer can also be prepared by laminating the second adhesive layer 2, the first substrate S and the first adhesive layer 1 in this order on a single side of the second substrate 3 (the side that has not been subjected to anti-reflection treatment and / or anti-glare treatment when such treatment has been performed).
[0336] After applying the solvent-based adhesive composition, the solvent is dried. As a drying method, an appropriate method can be appropriately adopted according to the purpose. The heating drying temperature is preferably 40°C to 200°C, more preferably 50°C to 180°C, and particularly preferably 70°C to 170°C. The drying time can be appropriately adopted. The drying time is preferably 5 seconds to 20 minutes, more preferably 5 seconds to 15 minutes, and particularly preferably 10 seconds to 10 minutes.
[0337] After the solvent-based adhesive composition is applied, it may be heated as necessary. The heating temperature and heating time may be appropriately set depending on the type of crosslinking agent used, and are generally in the range of 20° C. to 160° C. and about 1 minute to 7 days.
[0338] The first and second adhesive layers of the third embodiment preferably have the same thickness (respective thicknesses of the first and second adhesive layers, and thickness ratio), light transmittance, and shear storage modulus as those of the first and second adhesive layers of the first embodiment.
[0339] In addition, when the solvent-based adhesive composition contains the (meth)acrylic block copolymer A, the storage modulus (G'25) at 25°C of the first adhesive layer and / or the second adhesive layer (particularly the first adhesive layer) is not particularly limited. From the viewpoint of improving processability at room temperature, it is preferably 1 MPa or more, more preferably 1.5 MPa or more, more preferably 2 MPa or more, more preferably 2.5 MPa or more, more preferably 3 MPa or more, and from the viewpoint of improving adhesion reliability at room temperature, it is preferably 50 MPa or less, more preferably 45 MPa or less, more preferably 40 MPa or less, more preferably 35 MPa or less, and more preferably 30 MPa or less.
[0340] The storage modulus (G'50) at 50°C of the first adhesive layer and / or the second adhesive layer (particularly the first adhesive layer) when the solvent-based adhesive composition contains the (meth)acrylic block copolymer A is not particularly limited, but is preferably 0.5 MPa or less, more preferably 0.45 MPa or less, more preferably 0.4 MPa or less, more preferably 0.35 MPa or less, more preferably 0.3 MPa or less, from the viewpoint of improving the height difference absorbency in the region exceeding 50°C, and is preferably 0.0001 MPa or more, more preferably 0.0005 MPa or more, more preferably 0.001 MPa or more, more preferably 0.005 MPa or more, more preferably 0.01 MPa or more, from the viewpoint of improving the operability in the region exceeding 50°C.
[0341] The ratio of the storage modulus at 25°C to the storage modulus at 50°C (G'25 / G'50) of the first adhesive layer and / or the second adhesive layer (particularly the first adhesive layer) when the solvent-based adhesive composition contains the (meth)acrylic block copolymer A is not particularly limited. From the viewpoint of improving processability at room temperature and improving the height difference absorbency in the region exceeding 50°C, it is preferably 3 or more, more preferably 5 or more, more preferably 10 or more, further preferably 15 or more, and particularly preferably 20 or more. From the viewpoint of adhesion reliability, workability, etc., it is preferably 100 or less, more preferably 95 or less, more preferably 90 or less, further preferably 85 or less, and particularly preferably 80 or less.
[0342] It should be noted that the storage modulus at 25° C. (G′25), the storage modulus at 50° C. (G′25), and their ratio (G′25 / G′50) are measured by dynamic viscoelasticity measurement.
[0343] The optical laminate having the first pressure-sensitive adhesive layer and / or the second pressure-sensitive adhesive layer of the third embodiment containing a colorant has light absorption with respect to visible light.
[0344] The visible light transmittance of the optical layered body of the third embodiment is, for example, 80% or less, and may be 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, or 5% or less.
[0345] The optical laminate 10 of the present embodiment (first to third embodiments) may have release films respectively provided on the first adhesive layer and the second adhesive layer until use. In addition, the optical laminates 20 to 22 of the present embodiment (first to third embodiments) may have release films respectively provided on the first adhesive layer and the second adhesive layer until use.
[0346] The optical layered body of the present embodiment (first to third embodiments) may have a surface protection film laminated on the surface 3a of the second substrate 3. The surface protection film is suitable for preventing damage and dirt from attaching during the manufacture, transportation, and shipment of the optical layered body or an optical product including the optical layered body.
[0347] The optical laminate (first mode to third mode) of the present embodiment may have other layers on the surface or between any layers, such as substrates other than the first adhesive layer 1, the second adhesive layer 2, the first substrate S, the second substrate 3, the release film, and the surface protection film, within the range not impairing the effects of the present invention, such as substrates other than the first substrate and the second substrate 3, adhesive layers other than the first adhesive layer 1 and the second adhesive layer 2, intermediate layers, primer layers, etc.
[0348] <Self-luminous display device>
[0349] The second aspect of the present invention is a self-luminous display device that is a display device that arranges a large number of tiny light-emitting elements on a wiring substrate, and uses a light-emitting control means connected thereto to selectively emit light from each light-emitting element, thereby being able to directly display text, images, images and other visual information on a display screen by using the flickering of each light-emitting element. Examples of self-luminous display devices include: Mini / Micro LED display devices, organic EL (electroluminescent) display devices. The third aspect of the present invention is particularly suitable for use in manufacturing Mini / Micro LED display devices.
[0350] Figures 5 to 7 It is a schematic diagram (cross-sectional view) showing an embodiment of a self-luminous display device (Mini / Micro LED display device) of the second aspect of the present invention. The Mini / Micro LED display device 30 of this embodiment includes a display panel on which a plurality of LED chips 7 are arranged on a single side of a substrate 5, and an optical laminate 20. The surface on which the LED chips 7 are arranged on the aforementioned display panel is laminated with the first adhesive layer 1 of the optical laminate 20. In the Mini / Micro LED display device 31, the surface 3a of the second substrate 3 on which the second adhesive layer 2 is not laminated is subjected to an anti-reflection treatment and / or an anti-glare treatment 4. In the Mini / MicroLED display device 32, the surface 3a of the second substrate 3 on which the second adhesive layer 2 is not laminated is formed with an anti-glare layer 4a as an anti-glare treatment.
[0351] In this embodiment, a metal wiring layer 6 for sending a light emission control signal to each LED chip 7 is stacked on the substrate 5 of the display panel. Each LED chip 7 that emits light of each color of red (R), green (G), and blue (B) is alternately arranged on the substrate 5 of the display panel via the metal wiring layer 6. The metal wiring layer 6 is formed of a metal such as copper, which reflects the light emitted by each LED chip 7, reducing the image recognition. In addition, the light emitted by each LED chip 7 of each color of RGB will be mixed, and the contrast will be reduced.
[0352] In the Mini / Micro LED display device of the present embodiment, the first adhesive layer 1 encapsulates the LED chips 7 arranged on the display panel and the metal wiring layer 6. By making the visible light transmittance of the first adhesive layer 1 lower than the visible light transmittance of the second adhesive layer 2, sufficient light shielding is achieved in the visible light region. Since the first adhesive layer 1 with higher light shielding properties (lower transmittance) encapsulates the LED chips 7 without gaps, it is possible to prevent color mixing between the LED chips 7 and improve contrast. In addition, since the first adhesive layer 1 with higher light shielding properties (lower transmittance) also encapsulates the surface of the metal wiring layer 6, it is possible to prevent reflection caused by the metal wiring layer 6.
[0353] In this embodiment, the second adhesive layer 2 is laminated on the upper part (display image side) of each LED chip 7 arranged on the display panel through the first substrate S, and also functions as an interlayer filling material for bonding the second substrate 3. By making the visible light transmittance of the second adhesive layer 2 higher than the visible light transmittance of the first adhesive layer 1, it has sufficient transmittance in the visible light region. Since the second adhesive layer 2 with higher transmittance is located on the upper part (display image side) of each LED chip 7, the absorption of visible light emitted by each LED chip 7 can be suppressed to a lower level, the luminous efficiency is improved, and the image can be made brighter. In addition, since there is no need to increase the output power to increase the luminous brightness, the power consumption can be suppressed to a lower level.
[0354] As described above, the optical laminate of the present embodiment includes a first adhesive layer with higher light-shielding properties (lower transmittance), so even when a metal adherend is laminated on the first adhesive layer, it is possible to prevent reflection and gloss on the metal surface. The reflectivity of the visible light region of the 5° regular reflection of the substrate surface 3a when a metal adherend is laminated on the first adhesive layer of the optical laminate of the present embodiment is preferably 50% or less, more preferably 30% or less, further preferably 15% or less, and particularly preferably 10% or less. The glossiness of the substrate surface 3a when a metal adherend is laminated on the first adhesive layer of the optical laminate of the present embodiment (based on JIS Z 8741-1997) is preferably 100% or less, more preferably 80% or less, further preferably 60% or less, and particularly preferably 50% or less.
[0355] In addition, copper, aluminum, stainless steel, etc. can be used as the above-mentioned metal adherend.
[0356] In the Mini / Micro LED display device of this embodiment, the first substrate S is stacked between the first adhesive layer 1 and the second adhesive layer 2. According to this scheme, the first substrate S physically isolates the adhesive layer 1 from the second adhesive layer 2. For example, when the first adhesive layer 1 contains a colorant (especially a dye) as described above, the colorant can be prevented from moving to the second adhesive layer 2 to reduce the transmittance and reduce the luminous efficiency.
[0357] In the Mini / Micro LED display device of this embodiment, it is preferred that the visible light transmittance T1 of the first adhesive layer 1 and the visible light transmittance T S Meet T1 <T S That is, it is preferred that the visible light transmittance of the first substrate S is higher than the visible light transmittance of the first adhesive layer 1. By making the visible light transmittance of the first substrate S higher than the visible light transmittance of the first adhesive layer 1, sufficient transmittance is achieved in the visible light region. Since the first substrate S with higher transmittance is located above each LED chip 7 (the image display side), the absorption of visible light emitted by each LED chip 7 can be suppressed to a lower level, the luminous efficiency can be improved, and the image can be made brighter.
[0358] In addition, in the Mini / Micro LED display device of the present embodiment, when the surface 3a of the second substrate 3 is subjected to an anti-reflection treatment and / or an anti-glare treatment 4, the second substrate surface 3a is prevented from being degraded in visibility due to reflection of external light, image reflection, etc., or the aesthetics such as glossiness are adjusted. The Mini / Micro LED display device 22 of the present embodiment has an anti-glare layer 4a formed on the surface 3a of the substrate 3. The average inclination angle θa (°) of the anti-glare layer 4a of the Mini / Micro LED display device 22 of the present embodiment is the same as described above.
[0359] The self-luminous display device of this embodiment may have optical components other than the display panel and the optical laminate. The above-mentioned optical components are not particularly limited, and examples thereof include: polarizing plates, phase difference plates, anti-reflection films, viewing angle adjustment films, optical compensation films, etc. It should be noted that the optical components also include components (decorative films, decorative films, surface protection plates, etc.) that perform the functions of decoration and protection while maintaining the recognizability of the display device and the input device.
[0360] The Mini / Micro LED display devices 30 to 32 of the present embodiment can be manufactured by bonding display panels each having a plurality of LED chips arranged on one surface of a substrate to the first pressure-sensitive adhesive layer of the optical layered bodies 20 to 22 of the present embodiment.
[0361] Specifically, the pasting of the optical laminate having a display panel and the first adhesive layer and / or the second adhesive layer of the first mode can be implemented by laminating under heating and / or pressure. In the case of pasting the optical laminate having a display panel and the first adhesive layer and / or the second adhesive layer of the second mode, it can be implemented by laminating under heating and / or pressure and then performing photocuring. The photocuring can be performed in the same manner as the photocuring of the first adhesive layer and / or the second adhesive layer forming the above-mentioned first mode.
[0362] When the first adhesive layer and / or the second adhesive layer is formed by a solvent-based adhesive composition comprising a (meth)acrylic block copolymer A, the above-mentioned bonding is preferably performed by heating and pressurizing at a temperature of 50°C or above. By performing heating and pressurizing at a temperature of 50°C or above, the adhesive layer forms high fluidity, which can fully follow the height difference of the LED chips arranged on the substrate and fit tightly without gaps. The heating is performed at a temperature of 50°C or above, preferably at a temperature of 60°C or above, and more preferably at a temperature of 70°C or above. There is no particular limitation on pressurization, for example, it may be performed at a temperature of 1.5 atm or above, preferably at a temperature of 2 atm or above, and more preferably at a temperature of 3 atm or above. Heating and pressurizing may be performed, for example, using an autoclave or the like. After the Mini / Micro LED display device manufactured in this way is restored to room temperature (25°C), the storage modulus of the adhesive layer increases, and the processability and bonding reliability are improved.
[0363] Example
[0364] Hereinafter, the present invention will be described in more detail based on examples, but the present invention is not limited to these examples. It should be noted that various properties in the following production examples were evaluated or measured by the following methods.
[0365] (Surface shape measurement)
[0366] A glass plate (thickness 1.3 mm) manufactured by Matsunami Glass Industry Co., Ltd. was bonded to the surface of the anti-glare film where the anti-glare layer was not formed using an adhesive, and the surface shape of the anti-glare layer was measured using a high-precision fine shape measuring instrument (trade name; Surfcorder ET4000, manufactured by Kosaka Laboratory Co., Ltd.) under the condition of a cutoff value of 0.8 mm to obtain the average inclination angle θa. It should be noted that the high-precision fine shape measuring instrument automatically calculates the average inclination angle θa. The average inclination angle θa is based on JIS B 0601 (1994 edition).
[0367] (Haze)
[0368] The haze value was measured by the method specified in JIS K 7136, with the haze meter (manufactured by Murakami Color Research Laboratory Co., Ltd., trade name "HN-150") set so that light entered from the anti-glare surface of the anti-glare film.
[0369] (Visible light transmittance of adhesive sheet)
[0370] The release film on one side is peeled off from the adhesive sheet, and the alkali-free glass is bonded to the exposed surface. Then, the release film on the other side is peeled off from the adhesive sheet to obtain a sample with an adhesive sheet bonded to the alkali-free glass plate. Using this sample, the transmission spectrum of the evaluation sample is measured using a visible-ultraviolet spectrophotometer (manufactured by Hitachi High-Technologies Corporation, trade name "U-4100"). Using alkali-free glass (single substance) as the baseline, the ratio of the transmittance (amount of transmitted light) of the evaluation sample to the transmittance (amount of transmitted light) of the alkali-free glass is used as the transmittance of the adhesive sheet. Based on the transmission spectrum of the adhesive sheet, the transmittance T at a wavelength of 550nm is calculated. VIS .
[0371] (Visible light transmittance of anti-glare film)
[0372] The anti-glare film was placed on a spectrophotometer U4100 (manufactured by Hitachi High-Technologies Corporation) so that light was incident from the anti-glare layer side, and the transmittance (%) in the visible light region was measured. The transmittance is the Y value measured using a 2 degree viewing field (C light source) of JIS Z 8701 and corrected for visual sensitivity.
[0373] Production Example 1
[0374] (Preparation of Anti-glare Film)
[0375] As the resin contained in the anti-glare layer, 100 parts by weight of an ultraviolet curable urethane acrylate resin (manufactured by DIC Corporation, trade name "UNIDIC 17-806", solid content 80%) was prepared. With respect to 100 parts by weight of the resin solid content of the above resin, 14 parts by weight of styrene crosslinked particles (manufactured by Soken Chemical Co., Ltd., trade name "MX-350H", weight average particle size: 3.5 μm, refractive index 1.59) as light diffusing fine particles, 2.5 parts by weight of synthetic montmorillonite belonging to organic clay (manufactured by Kunimine Industries Co., Ltd., trade name "Sumecton San") as a thixotropic agent, 5 parts by weight of a photopolymerization initiator (manufactured by BASF, trade name "OMNIRAD907"), and 0.5 parts by weight of a leveling agent (manufactured by DIC Corporation, trade name "MEGAFAC F-556", solid content 100%) were mixed. The mixture was diluted with a toluene / ethyl acetate mixed solvent (weight ratio: 90 / 10) to a solid content concentration of 30% by weight to prepare a light diffusing element forming material (coating liquid).
[0376] On one side of a triacetyl cellulose (TAC) film (manufactured by Fujifilm Co., Ltd., product name "TG60UL", thickness: 60 μm) that can function as a protective layer, an anti-glare layer forming material (coating liquid) is applied using a rod coater to form a coating. Then, the transparent TAC film substrate formed with the coating is transported to a drying process. In the drying process, the coating is dried by heating at 110°C for 1 minute. Then, a high-pressure mercury lamp is used to irradiate the substrate with a cumulative light intensity of 300 mJ / cm 2 The coating was cured by ultraviolet light, and a light diffusion element with a thickness of 5.0 μm was formed on one side of the TAC film to obtain an anti-glare film 1. The haze value of the anti-glare film 1 was 42%. The θa (°) of the anti-glare layer of the anti-glare film 1 was 1.22. The visible light transmittance of the anti-glare film 1 was 90%.
[0377] Production Example 2
[0378] (Preparation of Anti-glare Film)
[0379] As light diffusing fine particles, 14 parts by weight of amorphous silica (manufactured by Fuji Silysia Chemical Ltd., trade name "SYLOPHOBIC 100", weight average particle size: 2.6 μm) was added to make the thickness after curing treatment 7.0 μm, and a light diffusing element was formed on one side of the TAC film by the same method as in Manufacturing Example 1 to obtain an anti-glare film 2. The haze value of the anti-glare film 2 was 11%. The θa (°) of the anti-glare layer of the anti-glare film 2 was 1.43. The visible light transmittance of the anti-glare film 2 was 91%.
[0380] Production Example 3
[0381] (Preparation of Anti-glare Film)
[0382] As the resin contained in the anti-glare layer forming material, 100 parts by weight of ultraviolet curing urethane acrylate resin (manufactured by DIC Corporation, trade name "UNIDIC 17-806", solid content 80%) was prepared. With respect to 100 parts by weight of the resin solid content of the above resin, 7 parts by weight of amorphous silica (manufactured by Fuji Silysia Chemical Ltd., trade name "SYLOPHOBIC 702"), 6.5 parts by weight of amorphous silica (manufactured by Fuji Silysia Chemical Ltd., trade name "SYLOPHOBIC 100"), 5 parts by weight of a photopolymerization initiator (manufactured by BASF, trade name "OMNIRAD184"), and 0.5 parts by weight of a leveling agent (manufactured by DIC Corporation, trade name "MEGAFAC F-556") were mixed as anti-glare layer forming particles. The mixture was diluted with toluene to a solid content concentration of 30% to prepare an anti-glare layer forming material (coating liquid).
[0383] As a light-transmitting substrate, a transparent plastic film substrate (TAC film, manufactured by Fuji Film Co., Ltd., trade name "TD80UL", thickness: 80 μm) is prepared. The anti-glare layer forming material (coating liquid) is formed into a coating film on one side of the transparent plastic film substrate using a rod coater. Then, the transparent plastic film substrate with the coating film formed is transported to a drying process. In the drying process, the coating film is dried by heating at 110°C for 1 minute. Then, a high-pressure mercury lamp is used to irradiate with a cumulative light amount of 300 mJ / cm 2 The coating film was cured by ultraviolet light to form an anti-glare layer with a thickness of 5.0 μm, thereby obtaining an anti-glare film 3. The θa (°) of the anti-glare layer of the anti-glare film 3 was 3.5. The visible light transmittance of the anti-glare film 3 was 91%.
[0384] Production Example 4
[0385] (Preparation of Anti-glare Film)
[0386] As anti-glare layer forming particles, 6.5 parts by weight of amorphous silica (manufactured by Fuji Silysia Chemical Ltd., trade name "SYLOPHOBIC 702"), 6.5 parts by weight of amorphous silica (manufactured by Fuji Silysia Chemical Ltd., trade name "SYLOPHOBIC 200"), and 2.5 parts by weight of a thickener (manufactured by Co-op Chemical Co., Ltd., trade name "LUCENTITE SAN") were added, and the thickness after curing was 8.0 μm. Anti-glare film 4 was obtained in the same manner as in Preparation Example 3. The θa (°) of the anti-glare layer of anti-glare film 4 was 2.3. The visible light transmittance of anti-glare film 4 was 91%.
[0387] Production Example 5
[0388] (Preparation of prepolymer)
[0389] Into a separable flask equipped with a thermometer, a stirrer, a reflux condenser and a nitrogen inlet tube, 67 parts by weight of butyl acrylate (BA), 14 parts by weight of cyclohexyl acrylate (CHA, manufactured by Osaka Organic Chemical Industry Co., Ltd., trade name "Viscoat#155"), 19 parts by weight of 4-hydroxybutyl acrylate (4-HBA), 0.09 parts by weight of a photopolymerization initiator (manufactured by BASF, trade name "IRGACURE 184") and 0.09 parts by weight of a photopolymerization initiator (manufactured by BASF, trade name "IRGACURE 651") were added, and nitrogen was introduced and nitrogen replacement was performed for about 1 hour while stirring. Then, the mixture was heated at 5 mW / cm 2 The polymerization was carried out by irradiating UVA, and the reaction rate was adjusted to 5 to 15% to obtain an acrylic prepolymer solution.
[0390] (Preparation of Adhesive Composition)
[0391] To the acrylic prepolymer solution obtained above (so that the total amount of the prepolymer is 100 parts by weight), 9 parts by weight of 2-hydroxyethyl acrylate (HEA), 8 parts by weight of 4-hydroxybutyl acrylate (4-HBA), 0.12 parts by weight of dipentaerythritol hexaacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd., trade name "KAYARAD DPHA") as a multifunctional monomer, and 0.35 parts by weight of 3-glycidoxypropyltrimethoxysilane as a silane coupling agent were added to prepare a photopolymerizable adhesive composition solution.
[0392] (Preparation of Adhesive Sheet)
[0393] The prepared photopolymerizable adhesive composition solution was applied to the release surface of a release film R1 (MRF#38, manufactured by Mitsubishi Resins Co., Ltd.) with a thickness of 38 μm and a release surface on one side of a polyester film so that the thickness after curing was 100 μm, and a release film R2 (MRE#38, manufactured by Mitsubishi Resins Co., Ltd.) with a release surface on one side of a polyester film was covered to block air. A black light (FL15BL, manufactured by Toshiba Corporation) was used to illuminate the laminate from one side at an illumination of 5 mW / cm 2 、Accumulated light quantity 1300mJ / cm 2 Thus, a 100 μm thick adhesive sheet 1 was obtained in the form of a substrate-free adhesive sheet, in which the photo-crosslinkable adhesive as a cured product of the black adhesive composition was sandwiched between the release films R1 and R2.
[0394] The visible light transmittance of the pressure-sensitive adhesive sheet 1 was 90%.
[0395] Production Example 6
[0396] (Preparation of Adhesive Polymer)
[0397] Into a reaction vessel equipped with a thermometer, a stirrer, a reflux condenser and a nitrogen inlet pipe, 63 parts by mass of 2-ethylhexyl acrylate (2EHA) as monomer components, 15 parts by mass of N-vinyl pyrrolidone (NVP), 9 parts by mass of methyl methacrylate (MMA), 13 parts by mass of 2-hydroxyethyl acrylate (HEA), 0.2 parts by mass of azobisisobutyronitrile as a polymerization initiator, and 233 parts by mass of ethyl acetate as a solvent were added, and nitrogen was introduced and nitrogen replacement was performed for about 1 hour while stirring. Then, the reaction was heated to 60°C for 7 hours to obtain a solution of an adhesive polymer having a weight average molecular weight (Mw) of 1,200,000.
[0398] The glass transition temperature of the adhesive polymer calculated by the FOX equation was -34°C.
[0399] (Preparation of Adhesive Composition)
[0400] To the adhesive polymer solution obtained above, 1.1 parts by mass of TAKENATE D-110N (a 75% ethyl acetate solution of trimethylolpropane adduct of xylylenediisocyanate, manufactured by Mitsui Chemicals) as a crosslinking agent and 0.5 parts by mass of a dye (NUBIAN Black PA-2802, manufactured by ORIENT CHEMICAL INDUSTRIES CO., LTD.) were added based on 100 parts by mass of the adhesive polymer in the adhesive polymer solution, and the mixture was mixed uniformly to prepare a black solution of a solvent-based adhesive composition.
[0401] (Preparation of Adhesive Sheet)
[0402] On one side of a polyethylene terephthalate film with a thickness of 50 μm and subjected to surface release treatment, a solution of the black solvent-based adhesive composition obtained above is applied by a dip roller in a manner that the thickness after drying is 25 μm, and the solvent is removed by drying at 130°C for 1 minute. An adhesive layer is thus formed. Furthermore, the release-treated surface of a peeling film (a polyethylene terephthalate film with a thickness of 25 μm and subjected to surface release treatment with silicone) is attached to the other side of the adhesive. Then, an aging treatment is performed for 4 days in an atmosphere of 25°C to perform a cross-linking reaction. Thus, an adhesive sheet 2 (25 μm adhesive layer) is obtained in the form of a substrate-free adhesive sheet.
[0403] The visible light transmittance of the pressure-sensitive adhesive sheet 2 was 55%.
[0404] Production Example 7
[0405] A PSA sheet 3 (25 μm thick PSA layer) was obtained in the same manner as in Production Example 6 except that a dye (NUBIAN Black PA-2802 manufactured by ORIENT CHEMICAL INDUSTRIES CO., LTD.) was not added.
[0406] The visible light transmittance of the adhesive sheet 3 was 90%.
[0407] Example 1
[0408] (Preparation of optical laminate)
[0409] The adhesive surface exposed by peeling off the release film on one side of the adhesive sheet 1 obtained in Production Example 5 was bonded to a TAC film 1 (thickness: 60 μm; visible light transmittance: 91%) cut into 50 mm×50 mm. Then, the release film on the other side was peeled off from the adhesive sheet 1, and the exposed adhesive surface was bonded to a TAC film 2 (thickness: 60 μm; visible light transmittance: 91%) cut into 50 mm×50 mm, and the adhesive surface exposed by peeling off the release film on one side of the adhesive sheet 2 obtained in Production Example 6 was further bonded to obtain an optical laminate 1 consisting of TAC film 1 / adhesive sheet 1 / TAC film 2 / adhesive sheet 2 / release film.
[0410] Example 2
[0411] (Preparation of optical laminate)
[0412] An optical laminate 2 consisting of TAC film 1 / adhesive sheet 1 / TAC film 3 / adhesive sheet 2 / release film was obtained in the same manner as in Example 1 except that TAC film 3 (thickness: 40 μm; visible light transmittance: 90%) was used instead of TAC film 2.
[0413] Example 3
[0414] (Preparation of optical laminate)
[0415] An optical laminate 3 consisting of TAC film 1 / adhesive sheet 1 / PET film 1 / adhesive sheet 2 / release film was obtained in the same manner as in Example 1 except that PET film 1 (thickness: 50 μm; visible light transmittance: 90%) was used instead of TAC film 2.
[0416] Example 4
[0417] (Preparation of optical laminate)
[0418] The same procedure as in Example 1 was carried out except that the pressure-sensitive adhesive sheet 3 was used instead of the pressure-sensitive adhesive sheet 1 to obtain an optical laminate 4 consisting of TAC film 1 / pressure-sensitive adhesive sheet 3 / TAC film 2 / pressure-sensitive adhesive sheet 2 / release film.
[0419] Example 5
[0420] (Preparation of optical laminate)
[0421] The same procedure as in Example 1 was carried out except that TAC film 3 was used instead of TAC film 2 and pressure-sensitive adhesive sheet 3 was used instead of pressure-sensitive adhesive sheet 1 to obtain an optical laminate 5 consisting of TAC film 1 / pressure-sensitive adhesive sheet 3 / TAC film 3 / pressure-sensitive adhesive sheet 2 / release film.
[0422] Example 6
[0423] (Preparation of optical laminate)
[0424] The same procedure as in Example 1 was carried out except that PET film 1 was used instead of TAC film 2 and pressure-sensitive adhesive sheet 3 was used instead of pressure-sensitive adhesive sheet 1 to obtain an optical laminate 6 consisting of TAC film 1 / pressure-sensitive adhesive sheet 3 / PET film 1 / pressure-sensitive adhesive sheet 2 / release film.
[0425] Comparative Example 1
[0426] (Preparation of optical laminate)
[0427] The adhesive surface exposed by peeling off the release film on one side of the adhesive sheet 1 obtained in Manufacturing Example 5 was bonded to a TAC film 1 cut into 50 mm×50 mm. Then, the adhesive surface exposed by peeling off the release film on the other side of the adhesive sheet 1 was bonded to the adhesive surface exposed by peeling off the release film on one side of the adhesive sheet 2 obtained in Manufacturing Example 6, to obtain an optical laminate 7 consisting of TAC film 1 / adhesive sheet 1 / adhesive sheet 2 / release film.
[0428] Comparative Example 2
[0429] (Preparation of optical laminate)
[0430] An optical laminate 8 consisting of TAC film 1 / adhesive sheet 3 / adhesive sheet 2 / release film was obtained in the same manner as in Comparative Example 1 except that the adhesive sheet 3 was used instead of the adhesive sheet 1.
[0431] (evaluate)
[0432] The following evaluations were performed using the optical layered bodies obtained in the above Examples and Comparative Examples. The evaluation methods are shown below.
[0433] (1) Evaluation of color shift
[0434] The optical laminates obtained in the examples and comparative examples were cut using a slicer after the initial and reliability tests, and the cut surfaces were observed using an optical microscope to confirm whether the black dye contained in the adhesive sheet 2 was color-shifted to the adhesive sheet 1 or 3 and changed its color to black. The evaluation of no color shift was 0, and the evaluation of color shift was ×. The results are shown in Table 1.
[0435] The reliability test was conducted by leaving the sample to stand for 350 hours in an environment of a temperature of 85° C. and a humidity of 85%.
[0436] (2) Visible light transmittance
[0437] The optical laminate obtained in the above-mentioned examples and comparative examples was placed in a spectrophotometer U4100 (manufactured by Hitachi High-Technologies Corporation) in a manner such that light was incident from the glass plate side, and the transmittance (%) in the visible light region was measured. The transmittance is the Y value measured using a 2 degree viewing field (C light source) of JIS Z 8701 and corrected for visual sensitivity. The results are shown in Table 1.
[0438] (3) Reflectivity
[0439] A plate obtained by laminating aluminum foil on a black acrylic plate was prepared. The adhesive surface exposed by peeling off the release film of the optical laminate obtained in the above-mentioned embodiment and comparative example was laminated on the aluminum foil side of the above-mentioned plate to prepare a sample. The obtained sample was set in a spectrophotometer U4100 (manufactured by Hitachi High-Technologies Corporation) in a manner that the anti-glare film / TAC film was located on the light source side, and the reflectivity (%) in the visible light region of 5° regular reflection was measured. The results are shown in Table 1.
[0440] [Table 1]
[0441] (Table 1)
[0442]
[0443] Example 7
[0444] (Preparation of optical laminate)
[0445] The adhesive surface exposed by peeling off the release film on one side of the adhesive sheet 1 obtained in Manufacturing Example 5 was bonded to the surface of the anti-glare film 1 obtained in Manufacturing Example 1 cut into 50 mm×50 mm without the anti-glare layer formed thereon. Then, the adhesive surface exposed by peeling off the release film on the other side of the adhesive sheet 1 was bonded to the TAC film 2 cut into 50 mm×50 mm, and further bonded to the adhesive surface exposed by peeling off the release film on one side of the adhesive sheet 2 obtained in Manufacturing Example 6, to obtain an optical laminate 9 consisting of anti-glare film 1 / adhesive sheet 1 / TAC film 2 / adhesive sheet 2 / release film.
[0446] Embodiments 8 to 10
[0447] (Preparation of optical laminate)
[0448] Optical laminates 10 to 12 each consisting of anti-glare films 2 to 4 / adhesive sheet 1 / TAC film 2 / adhesive sheet 2 / release film were obtained in the same manner as in Example 7 except that the anti-glare films 2 to 4 obtained in Production Examples 2 to 4 were used instead of the anti-glare film 1.
[0449] Various modifications of the present invention will be described below.
[0450] [Supplementary Note 1] A laminate having a laminate structure in which a first adhesive layer, a substrate and a second adhesive layer are laminated in this order,
[0451] The visible light transmittance T1 of the first adhesive layer and the visible light transmittance T2 of the second adhesive layer satisfy T1 <T2。
[0452] [Supplementary Note 2] The optical laminate according to Supplementary Note 1, wherein the visible light transmittance T1 of the first adhesive layer and the visible light transmittance T2 of the substrate are S Meet T1 <T S .
[0453] [Supplementary Note 3] The optical laminate according to Supplementary Note 1 or 2, wherein the visible light transmittance T1 of the first pressure-sensitive adhesive layer is 80% or less.
[0454] [Appendix 4] The optical layered body according to any one of Appendices 1 to 3, wherein the visible light transmittance T2 of the second pressure-sensitive adhesive layer is 85 to 100%.
[0455] [Appendix 5] The optical laminate according to any one of Appendices 1 to 4, wherein the first adhesive layer and the second adhesive layer are adhesive layers formed from an adhesive composition selected from a photocurable adhesive composition and a solvent-based adhesive composition.
[0456] [Supplementary Note 6] The optical laminate according to Supplementary Note 5, wherein the adhesive composition forming the first adhesive layer contains a colorant.
[0457] [Supplementary Note 7] The optical layered body according to Supplementary Note 5 or 6, wherein the pressure-sensitive adhesive composition contains an acrylic polymer.
[0458] [Supplementary Note 8] The optical layered body according to Supplementary Note 7, wherein the acrylic polymer contains a (meth)acrylic block copolymer.
[0459] [Supplementary Note 9] The optical layered body according to Supplementary Note 8, wherein the pressure-sensitive adhesive composition forming the first pressure-sensitive adhesive layer is a solvent-based pressure-sensitive adhesive composition containing a (meth)acrylic block copolymer.
[0460] [Appendix 10] The optical layered body according to any one of Appendices 1 to 9, wherein the thickness of the first pressure-sensitive adhesive layer is 10 to 300 μm.
[0461] [Appendix 11] The optical layered body according to any one of Appendices 1 to 10, wherein the thickness of the second pressure-sensitive adhesive layer is 1 to 500 μm.
[0462] [Appendix 12] The optical laminate according to any one of Appendices 1 to 11, wherein the ratio of the thickness of the second adhesive layer to the thickness of the first adhesive layer (thickness of the second adhesive layer / thickness of the first adhesive layer) is 1.0 to 5.0.
[0463] [Appendix 13] The optical layered body according to any one of Appendices 1 to 12, wherein a second substrate is further laminated on the surface of the second pressure-sensitive adhesive layer on which the substrate is not laminated.
[0464] [Appendix 14] The optical layered body according to Appendix 13, wherein the surface of the second substrate on which the second pressure-sensitive adhesive layer is not laminated is subjected to an anti-reflection treatment and / or an anti-glare treatment.
[0465] [Supplementary Note 15] The optical layered body according to Supplementary Note 14, wherein the anti-glare treatment is an anti-glare layer provided on one surface of the second substrate.
[0466] [Supplementary Note 16] The optical laminate according to Supplementary Note 14, wherein the anti-glare layer is formed using an anti-glare layer forming material comprising a resin, particles and a thixotropy imparting agent,
[0467] The anti-glare layer has aggregated portions forming convex portions on the surface of the anti-glare layer due to the aggregation of the particles and the thixotropy-imparting agent.
[0468] [Supplementary Note 17] The optical layered body according to Supplementary Note 16, wherein the average inclination angle θa (°) of the convex portions on the surface of the anti-glare layer is in the range of 0.1 to 1.5.
[0469] [Appendix 18] The optical layered body according to any one of Appendices 13 to 17, further comprising a surface protection film laminated on the surface of the second substrate on which the second pressure-sensitive adhesive layer is not laminated.
[0470] [Supplementary Note 19] A self-luminous display device, the self-luminous display device comprising:
[0471] A display panel having a plurality of light emitting elements arranged on one surface of a substrate, and
[0472] The optical layered body according to any one of Appendixes 1 to 18,
[0473] The surface of the display panel on which the light emitting elements are arranged is laminated with the first adhesive layer of the optical laminate.
[0474] [Supplementary Note 20] The self-luminous display device according to Supplementary Note 19, wherein the display panel is an LED panel in which a plurality of LED chips are arranged on a single surface of a substrate.
[0475] Industrial Applicability
[0476] The optical laminate of the present invention is suitable for encapsulating light-emitting elements of self-luminous display devices such as Mini / Micro LEDs.
[0477] Description of Reference Numerals
[0478] 10, 20, 21, 22 Optical laminate
[0479] 1 First adhesive layer
[0480] 2 Second adhesive layer
[0481] S First substrate
[0482] 3 Second substrate
[0483] 4 Anti-reflective treatment and / or anti-glare treatment
[0484] 4a Anti-glare layer
[0485] 30, 31, 32 Self-luminous display devices (Mini / Micro LED display devices)
[0486] 5 substrate
[0487] 6 Metal wiring layer
[0488] 7. Light-emitting element (LED chip)
Claims
1. An optical laminate having a laminate structure in which a first adhesive layer, a substrate and a second adhesive layer are laminated in this order, The visible light transmittance T1 of the first adhesive layer and the visible light transmittance T2 of the second adhesive layer satisfy T1 <T2, The first adhesive layer and the second adhesive layer are adhesive layers formed of an adhesive composition selected from a photocurable adhesive composition and a solvent-based adhesive composition, The adhesive composition forming the first adhesive layer contains a colorant, The colorant contains black pigment and / or black dye, When the first adhesive layer is formed of the photocurable adhesive composition, the black pigment is an ultraviolet-transmitting black pigment whose absorption of ultraviolet light is lower than that of visible light, and the black dye is an ultraviolet-transmitting black dye. The shear storage modulus of the first adhesive layer at a temperature of 85° C. is 3 to 300 kPa, The visible light transmittance of the substrate is 85-100%.
2. The optical layered body according to claim 1, wherein: The visible light transmittance T1 of the first adhesive layer and the visible light transmittance T S Meet T1 <T S .
3. The optical layered body according to claim 1 or 2, wherein: The visible light transmittance T1 of the first adhesive layer is 80% or less.
4. The optical layered body according to claim 1 or 2, wherein: The visible light transmittance T2 of the second adhesive layer is 85 to 100%.
5. The optical layered body according to claim 1, wherein: The adhesive composition contains an acrylic polymer.
6. The optical layered body according to claim 5, wherein: The acrylic polymer contains a (meth)acrylic block copolymer.
7. The optical layered body according to claim 6, wherein: The adhesive composition forming the first adhesive layer is a solvent-based adhesive composition containing a (meth)acrylic block copolymer.
8. The optical layered body according to claim 1 or 2, wherein: The thickness of the first adhesive layer is 10 to 300 μm.
9. The optical layered body according to claim 1 or 2, wherein: The second adhesive layer has a thickness of 1 to 500 μm.
10. The optical layered body according to claim 1 or 2, wherein: The ratio of the thickness of the second adhesive layer to the thickness of the first adhesive layer, that is, the thickness of the second adhesive layer / the thickness of the first adhesive layer, is 1.0 to 5.
0.
11. The optical layered body according to claim 1 or 2, wherein: A second substrate is further laminated on the surface of the second pressure-sensitive adhesive layer on which the substrate is not laminated.
12. The optical layered body according to claim 11, wherein: The surface of the second substrate on which the second pressure-sensitive adhesive layer is not laminated is subjected to an anti-reflection treatment and / or an anti-glare treatment.
13. The optical layered body according to claim 12, wherein: The anti-glare treatment is an anti-glare layer provided on one side of the second substrate.
14. The optical layered body according to claim 12, wherein: The anti-glare layer is formed using an anti-glare layer forming material including a resin, particles and a thixotropy imparting agent. The anti-glare layer has aggregated portions forming convex portions on the surface of the anti-glare layer due to the aggregation of the particles and the thixotropy-imparting agent.
15. The optical layered body according to claim 14, wherein: The average inclination angle θa (°) of the convex portions on the surface of the anti-glare layer is in the range of 0.1 to 1.
5. 16 . The optical laminate according to claim 11 , further comprising a surface protection film laminated on a surface of the second substrate on which the second pressure-sensitive adhesive layer is not laminated.
17. A self-luminous display device, comprising: A display panel having a plurality of light emitting elements arranged on one surface of a substrate, and The optical layered body according to any one of claims 1 to 16, The first adhesive layer of the optical laminate is laminated on the surface of the display panel where the light emitting elements are arranged.
18. The self-luminous display device according to claim 17, wherein: The display panel is an LED panel in which a plurality of LED chips are arranged on a single surface of a substrate.
Citation Information
Patent Citations
Cured coating film, Anti-reflection hard coating film using it, polarization plate and image display device
JP2008088309A
Antiglare hard coat film, manufacturing method of same, optical element, polarizing plate, and image display apparatus
JP2008090263A
Antiglare film, polarizing plate, image display apparatus, and method for manufacturing antiglare film
JP2017138620A
Light absorption layer contained in color filter for organic electroluminescence display and sheet using the same
JP2017203810A
display device
JP2018523854A